A method for preparing a porous scaffold for tissue regeneration

The liquid material is stirred and liquid nitrogen is added by dynamic freezing method to form a semi-solid ice slurry and freeze-dried, which solves the problem of uneven large-scale porous structures in the prior art, and realizes the preparation of a uniform isotropic porous scaffold, which is suitable for large-scale tissue regeneration.

CN118512654BActive Publication Date: 2025-03-07SUNSHINE INNOVATION CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311236866.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-07-27
Filing Date
2023-09-22
Publication Date
2025-03-07
Estimated Expiration
2043-09-22

AI Technical Summary

Technical Problem

The existing frozen casting method is difficult to prepare large-scale uniform isotropic porous structures, resulting in uneven structures of the porous scaffolds and cannot be suitable for repairing larger tissue defects.

Method used

Using dynamic freezing method, the pre-cooled liquid material is continuously stirred while gradually adding liquid nitrogen to form a semi-solid ice slurry, and freeze-dried after complete solidification to prepare a uniform porous scaffold.

Benefits of technology

The uniform isotropic structure of large-scale porous scaffolds is realized, which improves the controllability of porosity and pore size, and is suitable for large-scale tissue regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118512654B_ABST
    Figure CN118512654B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of tissue regeneration, and in particular to a method for preparing a porous scaffold for tissue regeneration, the method comprising: S101 dynamically freezing a precooled first mixture, the dynamic freezing method comprising adding liquid nitrogen to the first mixture while stirring to obtain a second mixture, the second mixture being in a semi-solid ice slurry state; S102 adding the second mixture to a mold and placing it until the second mixture is completely solidified to obtain a third mixture; S103 freeze-drying the third mixture to obtain the porous scaffold. The method for preparing the porous scaffold provided by the present invention is not limited by size and shape, the prepared porous scaffold has a uniform isotropic porous structure, and the porosity and pore size of the porous scaffold are controllable.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Priority application

[0002] This application claims priority to PCT international application PCT / CN2023 / 109525 “A porous scaffold, preparation method, and use thereof” filed on July 27, 2023, which is incorporated by reference in its entirety. Technical Field

[0003] The invention relates to the field of tissue regeneration, and in particular to a method for preparing a porous scaffold for tissue regeneration. Background Art

[0004] With the advent of tissue engineering, people have devoted themselves to developing various three-dimensional (3D) porous scaffolds or extracellular matrix (ECM) analogs, which can be applied in various medical fields to repair damaged body tissues. For example, in the past decade, Collagen porous scaffolds have been successfully applied to the repair of skin soft tissue defects. These scaffolds with interconnected microporous structures are considered to be effective in tissue regeneration because they can provide temporary 3D support for the ingrowth of new tissues while stimulating extensive regenerative activities. Techniques such as sacrificial templates, electrospinning and 3D printing have been used to manufacture various 3D porous scaffolds. Among them, the freeze casting method, also known as the ice template method, has attracted more and more attention because of its mild processing conditions that can maintain the activity of components, its wide range of material (including polymers, ceramics and metals) applicability, its controllable porous structure, and its environmental friendliness. However, due to physical limitations such as heat conduction, traditional freeze casting methods often have difficulty in ensuring uniform freezing conditions throughout a large-sized (over the centimeter scale) frozen sample, resulting in the uneven structure of the obtained porous scaffold, which is specifically manifested as a short-range ordered multi-domain pore structure with random orientation. In other words, the existing freeze casting method has poor scalability and cannot prepare large-scale scaffolds with uniform isotropic porous structures, that is, the scaffolds prepared by the existing methods are difficult to use in the repair of larger tissue defects. Summary of the invention

[0005] In a first aspect, the present invention provides a method for preparing a porous scaffold, characterized in that the method comprises:

[0006] S101 dynamically freezes the precooled first mixture, wherein the dynamic freezing method includes adding liquid nitrogen to the first mixture while stirring to obtain a second mixture, wherein the second mixture is in a semi-solid ice slurry state, wherein the volume of the liquid nitrogen is 2-3 times the volume of the first mixture, and the stirring includes a first stirring stage and a second stirring stage; in the first stirring stage, a first volume of the liquid nitrogen is added and stirred at a first stirring rate for t1 time, and in the second stirring stage, a second volume of the liquid nitrogen is added and stirred at a second stirring rate for t2 time;

[0007] S102 adding the second mixture into a mold and placing the mold until the second mixture is completely solidified to obtain a third mixture;

[0008] S103 freeze-drying the third mixture to obtain the porous scaffold;

[0009] Wherein, the first mixture includes an aqueous solution or suspension of the biologically active material, the addition rate of the liquid nitrogen includes 0.5-10 mL / min, the first stirring rate includes 200-300 rpm, the t1 time includes 2-5 min, and the first volume includes 30%-45% of the volume of the liquid nitrogen; the second stirring rate includes 400-600 rpm, the t2 time includes 5-8 min, and the second volume includes 55%-70% of the volume of the liquid nitrogen.

[0010] The preparation method of the porous scaffold provided by the present invention is not limited by size and shape, the prepared porous scaffold has a uniform isotropic porous structure, and the porosity and pore size of the porous scaffold are controllable.

[0011] The present invention dynamically freezes the liquid material (also understood as the "first mixture"), that is, while continuously stirring the liquid material, a suitable proportion of liquid nitrogen is relatively slowly added thereto, thereby realizing the transformation of the liquid material into a semi-solid ice slurry. On the one hand, under the condition of the shearing effect generated by continuous stirring, the large temperature difference between the liquid nitrogen and the liquid material causes the formation of fine solid phase ice crystals in the liquid material. If the proportion of liquid nitrogen is too high, the liquid material will be directly frozen into solid ice, and semi-solid ice slurry cannot be formed; if the proportion of liquid nitrogen is too low, the proportion of solid phase ice crystals in the liquid material is too small, and it is closer to liquid, and even if it is subsequently solidified and freeze-dried, a uniform porous structure cannot be formed. On the other hand, with the relatively slow addition of liquid nitrogen (that is, the addition rate of liquid nitrogen is mainly affected by the actual volume of the first mixture, when the actual volume of the first mixture is high, the addition rate of liquid nitrogen will also increase accordingly, but it is "slowly added" relative to the first mixture with a higher volume), the uniform formation of fine ice crystals in the liquid material is guaranteed to a certain extent. If the rate of adding liquid nitrogen is too fast, part of the liquid material in direct contact with the liquid nitrogen will freeze quickly and generate large ice cubes, while the other part of the liquid material will remain in liquid state due to the inability to contact the liquid nitrogen, which will interfere with the uniformity of the ice crystals in the semi-solid ice slurry. In addition, during the dynamic freezing process, due to continuous stirring and continuous addition of liquid nitrogen, gas (such as air and nitrogen) is introduced into the liquid material, so that the liquid material (and the semi-solid ice slurry) has a certain volume of uniformly distributed bubbles, which ensures the porosity of the porous support to a certain extent. The continuous stirring of the present invention not only helps to homogenize the entire system, but also prevents the formation of large ice crystals. That is to say, even if large ice crystals are formed in some areas of the system, the continuous stirring of the present invention can break the large ice crystals into small ice crystals, thereby ensuring that the small ice crystals are evenly distributed in the formed semi-solid ice slurry. Specifically, the present invention initially stirs the liquid material for t1 time at a lower first stirring rate, so that the temperature of the liquid material can gradually approach the temperature of liquid nitrogen at a suitable speed, and ice crystals are formed under the action of liquid nitrogen; and the higher second stirring rate can better stir the liquid material with higher viscosity due to the increase in the generation of solid-phase ice crystals (or the transition state of the liquid material to semi-solid ice slurry). In addition, the second stirring rate can further ensure the homogenization of the system and the uniform dispersion of heat, thereby ensuring the uniform generation and dispersion of ice crystals. Then, the second stirring rate is maintained for t2 time, which can ensure that the liquid material is controlled and maintained in a semi-solid ice slurry state as a whole and bubbles are further introduced, so that the generated semi-solid ice slurry forms a three-phase coexistence structure in which nearly spherical ice crystals (solid state) and bubbles are uniformly dispersed in the liquid phase matrix, which provides a basis for the subsequent formation of a uniform porous structure.

[0012] In some embodiments, the precooling temperature includes 2-4° C. The precooling temperature ensures that the first mixture is in a liquid state before contacting liquid nitrogen, and also ensures a suitable temperature difference between the first mixture and its freezing point (freezing point), thereby avoiding a large temperature difference between the solidified part and the unsolidified part when adding liquid nitrogen for rapid cooling, thereby destroying the structural uniformity of the obtained semi-solid ice slurry.

[0013] In some embodiments, the dynamic freezing is performed under a temperature condition that can avoid volatilization of liquid nitrogen and melting of the second mixture to a certain extent, such as room temperature (eg, 15-25° C.).

[0014] In some embodiments, the dynamic freezing can be performed under air or an inert atmosphere.

[0015] In some embodiments, the second mixture is placed at -30°C–-10°C. At a temperature of -30°C–-10°C, the pre-existing uniformly distributed fine ice crystals in the semi-solid ice slurry grow until they merge with each other, and after complete solidification, a solidified structure (i.e., the third mixture) having an equiaxed ice crystal structure is formed. At the same time, during the solidification process, the raw material components (such as polymer molecules, etc.) corresponding to the semi-solid ice slurry are repelled by the ice crystals and compressed and gathered in the gaps between the ice crystals. Unexpectedly, the present invention has discovered that the present invention can separate the "nucleation" and "growth" processes of ice crystals by dynamically freezing the liquid material. That is, the method provided by the present invention can control the "nucleation" of ice crystals to a certain extent during the preparation process of the semi-solid ice slurry, and control the "growth" of ice crystals during the solidification process of the semi-solid ice slurry, thereby forming a solidified structure having an equiaxed ice crystal structure. The "nucleation" and "growth" processes of ice crystals in the traditional freeze casting process occur continuously and are difficult to control. Most of the solidified structures obtained in the end are columnar ice crystals. When freeze-dried, they can only form an uneven, anisotropic porous structure on a smaller scale. In summary, the present invention can achieve the transformation of the solidified structure from columnar ice crystals to equiaxed ice crystals, and is not affected by the size and shape of the semi-solid ice slurry, because it avoids the problem that the scaffolds generated by the conventional freeze casting process in the prior art cannot control the porous structure in large-scale production.

[0016] In some embodiments, the freeze-drying exemplary method includes setting the sample chamber temperature to -10°C - 20°C and the cold trap temperature to -80°C - -60°C.

[0017] In some embodiments, the freeze-drying time comprises 48-96 hours.

[0018] As the third mixture is freeze-dried, equiaxed ice crystals evenly distributed in the third mixture sublime, thereby forming a uniform porous scaffold structure.

[0019] In some embodiments, the stirring further comprises a third stirring stage, wherein the third stirring stage comprises adding an additional third volume of the liquid nitrogen to the first mixture and stirring at a third stirring rate for a time of t3, wherein the third stirring rate comprises 900-1200 rpm, the t3 time comprises 5-8 min, and the third volume comprises 45%-55% of the total volume of the liquid nitrogen added in the first stirring stage and the second stirring stage. The present invention finds that the porosity of the porous scaffold can be adjusted by increasing the stirring rate, and when a porous scaffold with a higher porosity is required, the stirring rate can be increased to the third stirring rate to introduce more bubbles into the semi-solid ice slurry, thereby increasing the porosity of the porous scaffold.

[0020] In some embodiments, the bioactive material comprises a biocompatible polymer material or a bioactive ceramic material. In some embodiments, the biocompatible polymer material comprises polyurethane, hyaluronic acid, alginic acid, gelatin, collagen, elastin, fibronectin, polylactic acid, polyglycolic acid, lactide-co-glycolide copolymer, glycosaminoglycan, proteoglycan, chondroitin, cellulose, agarose, carboxymethyl cellulose, chitin, or chitosan. In some embodiments, the bioactive ceramic material comprises tricalcium phosphate, hydroxyapatite or tetracalcium phosphate.

[0021] In some embodiments, the first mixture includes an aqueous polyurethane emulsion, a hyaluronic acid solution, an alginate solution, or a hydroxyapatite suspension.

[0022] It has been experimentally verified that the preparation method of the porous scaffold provided by the present invention is based on different material systems (such as the above-mentioned biocompatible polymer materials and bioactive ceramic materials), and can achieve large-scale preparation of isotropic uniform porous structures, which is suitable for application in fields such as tissue regeneration.

[0023] In some embodiments, the biocompatible polymer material is PEG-based waterborne polyurethane (ie, PEG-WPU).

[0024] In some embodiments, the percentage of PEG in the PEG-based aqueous polyurethane to the polyurethane soft segment content is 15-30 mol % (molar ratio).

[0025] In addition, the pore size of the porous scaffold can be adjusted by adjusting the concentration (or solid content) of the liquid material. When a porous scaffold with a smaller pore size is required, the solid content of the semi-solid ice slurry can be increased to reduce the pore size of the porous scaffold.

[0026] In some embodiments, the concentration (solid content) of the PEG-based aqueous polyurethane emulsion comprises 10-40 wt %.

[0027] In some embodiments, the concentration (solid content) of the PEG-based aqueous polyurethane emulsion comprises 14±2 wt %.

[0028] In a second aspect, the present invention further provides a porous patch for tissue regeneration, characterized in that the patch comprises:

[0029] A bottom support layer, wherein the bottom support layer comprises the porous support prepared by the above-mentioned preparation method;

[0030] a top barrier layer, the top barrier layer being used to protect the bottom support layer and / or provide mechanical support for the bottom support layer;

[0031] The thickness of the bottom support layer is 2-10 mm, and the thickness of the top barrier layer is 0.2-0.8 mm. As described above, the preparation method of the porous support provided by the present invention is not limited by size and shape. Therefore, the thickness and area of ​​the porous patch provided by the present invention can be customized according to actual conditions (such as the depth of the defect) (for example, adjusting the mold used to carry the second mixture) to meet the needs of wounds in different scenarios. The thickness of the top barrier layer can ensure the protection of the bottom support layer and / or provide mechanical support for the bottom support layer.

[0032] In some embodiments, the porous scaffold layer has a thickness comprised between 2-5 mm.

[0033] In some embodiments, the top barrier layer may be made of one or more of the following polymers: PCL-based WPU, PCL, and PLGA.

[0034] In some embodiments, the top barrier layer is prepared by coating the polymer emulsion onto the porous support layer and then drying the polymer emulsion, wherein the solid content of the polymer emulsion comprises 50-70 wt %.

[0035] In some embodiments, the drying temperature comprises 40°C - 80°C.

[0036] In some embodiments, the porous scaffold layer has a porosity of 80-95%.

[0037] In some embodiments, the porous scaffold has a pore size comprised between 50-150 μm.

[0038] Unexpectedly, the present invention found that the porous scaffold prepared by the present invention has a similar structure to the natural extracellular matrix. When applied to a wound (e.g., a deep oral mucosal defect), the porous scaffold prepared by the present invention can be used as a part of the missing tissue at the wound, promoting tissue reconstruction while hindering scar formation caused by inflammation and / or wound contraction, promoting wound healing and tissue regeneration, and is suitable for the healing of wounds such as skin and mucosa. It has been verified that the newly generated tissue at the wound (e.g., mucosal defect) treated with the scaffold of the present invention is closer to normal tissue and has almost no scar.

[0039] As used herein, the term "biological tissue" or "tissue" refers to any tissue of a living or dead organism or any tissue derived from a living or dead organism. Biological tissue can include any single tissue (e.g., a collection of cells that can be interconnected) or a group of tissues that make up an organ or part or region of an organism. Biological tissue includes one or more animal tissues of mucosal tissue, epidermal tissue, dermal tissue, and subcutaneous tissue. Different biological tissues can form organs with specific functions. The organism (i.e., subject or individual) to which the biological tissue is related or derived can be any animal, including mammals and non-mammals (e.g., invertebrates). Biological tissue can be complete, or can have one or more incisions, cracks, defects, or other types of wounds. In some embodiments, the biological tissue is a mammalian tissue.

[0040] As used herein, "wound" refers to a physical disruption of the continuity or integrity of a biological tissue structure. A wound may be caused by a cut, abrasion, avulsion, tear, puncture, cancer, diabetic ulcer or lesion, burn, surgery or other injury.

[0041] As used herein, "wound healing" refers to the partial or complete recovery of tissue integrity. In certain embodiments, the tissue is skin, that is, the wound is a skin wound, such as a dermal or epidermal wound. In certain embodiments, the tissue is mucosa, that is, the wound is a mucosal defect, and the mucosa includes nasal mucosa, oral mucosa, gastrointestinal mucosa, rectal mucosa, urethral mucosa, conjunctiva, glandular mucosa (e.g., mammary mucosa, epithelial mucosa). In certain embodiments, wound healing includes a healing program in time and space, and the program includes wound closure and a process related to wound closure. "Promoting wound healing" should be understood as restoring tissue from the interruption of continuity or integrity. In certain embodiments, promoting wound healing includes reaching the same degree of healing, and the required healing time is shorter. In certain embodiments, promoting wound healing includes reaching a higher degree of healing within the same healing time.

[0042] As used herein, "scar" refers to the appearance and pathological changes of tissues caused by trauma, which are the inevitable product of the body's wound repair process. When scar growth exceeds a certain limit, various complications may occur (such as destruction of appearance and functional activity disorders, etc.), causing great physical and mental pain to the patient (especially scars left after burns, scalds, and severe trauma). "Scarless healing" means less, significantly less or no scars formed by natural wound healing.

[0043] As used herein, the term "biocompatibility" refers to a material that is substantially non-toxic in the in vivo environment in which it is intended to be used and is substantially not rejected by the physiological system of an individual. The evaluation of the biocompatibility of a biomaterial should follow the two principles of biosafety and biofunctionality, requiring that the biomaterial has very low toxicity and that the biomaterial can appropriately stimulate the corresponding function of the body in a specific application (e.g., the interaction between the material and the body environment).

[0044] As used herein, "regeneration" is a repair process in which a tissue or organ is partially lost due to external influences, and a structure that is morphologically and / or functionally identical to the lost part grows based on the remaining part. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.

[0046] Figure 1 The semi-solid freeze casting method provided by the present invention for large-scale manufacturing of porous tissue regeneration scaffolds and the schematic diagram of constructing a bionic multi-layer patch to promote scar-free healing of large-area deep mucosal defects are shown;

[0047] Figure 2 The process flow of the semi-solid freeze casting method and the schematic diagram of preparing a porous WPU multilayer patch for oral mucosa regeneration using the method are shown;

[0048] Figure 3 The results of in vivo evaluation of WPU patch in promoting scarless healing of large deep oral mucosal defects in a porcine model are shown;

[0049] Figure 4a Hematoxylin and eosin (H&E) staining showing the progress of defect healing under different treatment conditions is shown;

[0050] Figure 4bThe immune response evaluation 14 days after surgery is shown;

[0051] Figure 5a GO analysis of WPU-treated versus control and dECM-treated groups is shown;

[0052] Figure 5b KEGG analysis of WPU-treated versus control and dECM-treated groups is shown;

[0053] Figure 6 shows the evaluation of scar-free oral mucosal remodeling after WPU mesh treatment;

[0054] Figure 7 shows the failure of conventional freeze-cast porous scaffolds in scaling up to achieve uniform pore formation;

[0055] Figure 8 Shown with Figure 2 The EDX spectra corresponding to the positions of asterisks in C are used to identify “polymer” and “ice”, respectively;

[0056] Fig. 9 A large-scale porous scaffold formed by semi-solid freeze casting is shown;

[0057] Fig.10 The simulation study of the solidification of water-based material system at different nucleation densities (including the simulated temperature field and the evolution of solidification structure) is shown;

[0058] Fig.11 The difference between conventional freezing and the semi-solid freezing of the present invention is shown;

[0059] Fig.12 It is shown that the semi-solid freeze casting method of the present invention is applicable to different types of material systems to construct large-scale isotropic uniform porous scaffolds;

[0060] Fig.13 The synthetic routes of PEG-WPU and PCL-WPU are shown;

[0061] Fig.14 The performance test of PEG-based WPU scaffold is shown;

[0062] Fig.15 F-actin staining (rhodamine-labeled phalloidin) of cells cultured in PEG25-WPU scaffolds is shown;

[0063] Fig.16 The evaluation of the patch effect of WPU multilayer patch in promoting cell adhesion, migration and macrophage M2 polarization in vitro is shown;

[0064] Fig.17shows the evaluation results after PEG15-WPU stent implantation;

[0065] Fig.18 Shown are histological sections of a large deep oral mucosal defect model in a pig;

[0066] Fig.19 SEM images of the cross-section (A and B), top surface (C, facing the oral cavity), and bottom surface (D, facing the defect) of a commercial dECM scaffold are shown;

[0067] Fig. 20 The figure shows that after the animals were sacrificed on the 28th day after treatment, the buccal mucosa was separated along the upper and lower jaws (red dotted lines) and the mucosal width in the relaxed state was measured (once the scar contracts, the width will decrease, so the relative mouth opening is determined based on the width of the buccal mucosa);

[0068] Fig.21 Ki-67 in the basal layer + Immunofluorescence images and quantification of proliferating cells (the yellow dashed line indicates the basal layer. Pig, n = 3. Data are expressed as mean ± SD, analyzed by one-way ANOVA, *P < 0.05, **P < 0.01, ***P < 0.001);

[0069] Fig. 22 Results of a three-month postoperative follow-up evaluation of mucosal remodeling are shown;

[0070] Fig.23 Shown is a histological comparison of common experimental animals and human oral mucosa (H&E staining);

[0071] Fig.24 The effects of the maximum stirring rate (A1, 600 rpm; A2, 1100 rpm) and freezing method (B1, direct method, mixing with LN2; B2, indirect method, -80 °C ice bath) during the semi-solid slurry preparation on the final porous morphology of the scaffold are shown;

[0072] Fig.25 H&E staining of skin wounds at days 7 and 14 after surgery is shown;

[0073] Fig.26 The effect of the solid content of WPU (15wt%, 25wt%, 40wt%) on the final porous morphology of the scaffold is shown;

[0074] Fig. 27 The structural formula of PEG-based WPU is shown. DETAILED DESCRIPTION

[0075] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0076] In this document, the terms "upper", "lower", "inner", "outer", "front", "back", "one end", "the other end" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0077] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0078] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0079] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0080] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0081] In this specification, certain embodiments may be disclosed in a format of being in a certain range. It should be understood that such description of "being in a certain range" is merely for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the description of the range 1 to 6 should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as individual numbers within this range, such as 1, 2, 3, 4, 5 and 6. Regardless of the breadth of the range, the above rules apply.

[0082] Detailed description with attached drawings:

[0083] Figure 1 :The semi-solid freeze casting technology of the present invention realizes the large-scale manufacturing of isotropic uniform porous scaffolds in a water-based material system, aiming to promote large-scale tissue engineering applications. Based on the prepared isotropic uniform porous scaffold, a large-sized porous WPU patch with a bio-simulated multilayer structure is prepared for large-scale oral mucosal reconstruction. Schematic diagram of the mechanism of nearly regenerative scarless oral mucosal reconstruction mediated by the WPU patch, involving a series of coordinated healing processes occurring in the inflammatory phase, the proliferation phase, and the remodeling phase. In contrast, the contraction-dependent healing process often leads to scar contracture.

[0084] Figure 2 : Figure 2 The process flow of the semi-solid freeze casting method provided by the present invention is shown. (A) describes the key "phase transition" of the starting frozen material (taking WPU emulsion as an example) from a liquid suspension typically used in traditional freeze casting to a semi-frozen ice slurry used for semi-solid freeze casting; the semi-frozen ice slurry (or semi-frozen slurry) is a three-phase mixture of solid, liquid and air. Figure 2 A shows photographs of the WPU emulsion and the resulting semi-solid WPU ice slurry. (B) Provides microstructural and rheological evidence for the semi-solid nature of the WPU ice slurry. Optical micrographs show the microstructure of the semi-solid slurry, which includes bubbles (indicated by white arrows) and nearly spherical primary ice crystals (indicated by red arrows) dispersed in a semi-frozen liquid matrix. Rheological data confirm the shear thinning behavior of the ice slurry. (C) Cross-sectional observations of the solidified ice slurry were performed using cryo-SEM (equipped with an energy dispersive spectrometer (EDS)) to analyze the ice crystal morphology and identify the distribution of polymer (marked with yellow asterisks) and ice (marked with red asterisks). (D) The left panel shows the preparation of the WPU porous thin layer scaffold, which was subsequently used to make a multilayer patch. The right panel shows the ease of linear expansion of the porous thin layer scaffold achieved by semi-solid freeze casting, for example, the area of ​​the scaffold was expanded to 760 cm 2. SEM images of five representative sampling locations show the uniformity of the entire porous structure. (E) The shape and size of the unrelated specimens are highlighted, and the consistency of the uniform porous structure in the scaffolds produced by semi-solid freeze casting is confirmed by micro-CT. Pseudo-color obtained from orientation analysis using ImageJ software shows that semi-solid freeze casting achieves an isotropic single-domain porous structure, which is in contrast to the multi-domain oriented structure with short-range order observed in traditional processes. (F) The biomimetic porous WPU multilayer patch designed by the present invention is highly similar to the natural oral mucosa (for example, as shown in Masson's trichrome sections of porcine buccal mucosa, loose submucosal ECM and dense epidermal barrier). Figure 2 F contains SEM images of the cross section, dense top surface and porous bottom surface of the patch in the dry state, and confocal laser scanning microscopy (CLSM) image of the cross section of the patch in the swollen state.

[0085] Figure 3 : (A) Schematic diagram of the study of the healing process of oral mucosal defects. (B) A general photograph depicting the healing process. Day 28 after surgery: (C) Relative mouth opening compared to normal pigs (measurement method see Fig. 20 ). (D) The hardness of the newly formed mucosa was measured using a C-type Shore durometer. (E) Histological images (H&E staining) show that scar contracture occurred in the control and dECM-treated defects, while the WPU patch-treated defects showed mucosal tissue regeneration. The dotted line marks the defect boundary. The green box shows the outline of the reconstructed epidermis in (F), observed by keratin 19 immunohistochemical staining; the yellow box shows the morphology of highly elongated fibroblasts in the contracture scar tissue in (H). Histological evaluation of the regenerated matrix (composed of the lamina propria and submucosal layer) included: (G) Evaluation of collagen fiber structure using Masson's trichrome staining and fiber orientation analysis. (H) Examination of fibroblast morphology. (I) Based on the H&E images, the width of the newly formed granulation tissue was measured to compare oral cheek contracture. (J) The orientation distribution curve corresponding to the orientation pseudocolor map in (G) is shown. Three pigs were included in each group. Data are expressed as mean ± standard deviation (SD). Statistical significance in (C), (D) and (I) was determined by one-way analysis of variance (ANOVA) with the following symbols: nsP>0.05, *P<0.05, **P<0.01, ***P<0.001.

[0086] Figure 4: Figure 4a : (A) Hematoxylin and eosin (H&E) staining shows the progress of defect healing under different treatment conditions. The dotted line indicates the boundary of the defect. The blue arrow highlights the front of the migrating epidermal tissue in the defect treated with WPU patch. Figure 4b:(BD) Immunofluorescence images of defect sites and CD68 + / CD86 + Macrophages (B), CD3 + Quantification of T cells (C) and proinflammatory cytokine IL-17 (D). (E) Gene set enrichment analysis (based on RNA-seq data) illustrates representative Kyoto Encyclopedia of Genomes (KEGG) pathways related to immune regulation that showed significant changes in defects treated with WPU patches compared with the control or dECM-treated groups. Hierarchical clustering heat maps show differentially expressed genes (DEGs) in these KEGG pathways, and pie charts show the percentages of downregulated and upregulated genes. (F) Inflammatory genes downregulated after WPU patch treatment were validated by reverse transcription-polymerase chain reaction (RT-qPCR). ACTIN was used as an internal reference gene; the gene expression of the dECM and WPU groups was normalized to the expression level of each target gene in the control group and the relative expression level of each gene was calculated. Data are presented as mean ± standard deviation (SD). In (B2), (C2), (D2) and (F), statistical significance was determined by one-way analysis of variance (ANOVA), ns indicates P>0.05, * indicates P<0.05, ** indicates P<0.01, and *** indicates P<0.001.

[0087] Figure 5: Figure 5a : (AC) GO pathways belonging to the wound response (A), collagen matrix deposition (B), and epithelialization (C) gene modules were significantly altered in WPU patch-treated defects based on RNA-seq data compared with control or dECM-treated defects (representative GO terms in these modules are shown here). Hierarchical clustering heatmaps show the DEGs found in the corresponding modules, and pie charts show the percentage of down-regulated and up-regulated genes. Figure 5b :(D) KEGG enrichment analysis showed that multiple pathways related to wound repair were significantly altered in defects treated with WPU patches compared with those treated with control or dECM. The heat map showed that most genes in the significantly altered KEGG pathways were significantly upregulated after WPU patch treatment, and these pathways converged on promoting proliferation and anti-apoptosis to accelerate wound healing, as shown in Figure (E). Red and pink arrows marked the genes that were significantly upregulated in different comparison groups. (F) RT-qPCR verified several key upregulated genes in the WPU group. ACTIN was used as an internal reference gene; the gene expression of the dECM group and the WPU group was normalized based on the expression level of each target gene in the control group, and the relative expression level of each gene was calculated. Pig, n = 3. Data are expressed as mean ± SD, *P < 0.05, **P < 0.01, ***P < 0.001, (F) is one-way analysis of variance.

[0088] Figure 6 : (AC) Immunofluorescence images and quantification of α-SMA (A), TGF-β (B), and collagen types I and III (C) in the regenerated mucosal matrix. Dashed lines indicate the contracted defect boundary. (D) Hierarchical clustering heatmap showed that DEGs associated with collagen matrix formation were downregulated 28 days after surgery in defects treated with WPU patches. (E) RT-qPCR validated the sequential changes of genes involved in the transition from proliferation (day 14) to scarless remodeling (day 28). Pigs, n = 3. Data are presented as mean ± SD, according to one-way ANOVA in (A2), (B2), (C2), and (E), nsP>0.05, *P<0.05, **P<0.01, ***P<0.001.

[0089] Figure 7 :SEM images show small size (10×10×3mm 3 ) The relatively uniform porous structure in the scaffold. Large size scaffold (4×3×3cm 3 ) Representative micro-CT image of a cross section showing the heterogeneous structure from the surface to the center. Pseudo-coloring of the orientation analysis shows the presence of multiple small-scale short-range ordered orientation domains within a large-scale sample.

[0090] Fig. 9 : (A) Scaffolds with greater thickness (more than 2 cm) show uniform porosity throughout the sample as determined by micro-CT and orientation analysis. (B) Scaffolds with irregular shapes also show consistent uniform porosity.

[0091] Fig.10 :(A) ProCAST software was used to simulate the temperature field of the solidification process of a 4℃ aqueous system frozen in a -20℃ constant temperature environment. (B) The simulation study revealed that with the increase of nucleation density, the microstructure of the solidified structure after freezing changes from columnar crystals to equiaxed crystals. Low nucleation density (i, 1×10 7 m -3 ) and high nucleation density (iii, 1×10 13 m -3 ) under the solidification process.

[0092] Fig.11 :(A) Cooling curves of WPU emulsion (conventional) and WPU slurry (semi-solid) frozen at -80℃. The lower freezing temperature was set to better observe the re-calendering phenomenon, thereby revealing the difference between the two freezing methods. The temperature at the center of the sample was recorded using a thermal resistor. Sample size: 2.5×2.3×2.3cm 3(B) Schematic diagram of ice crystal growth. i. In conventional freezing, ice crystals continue to grow in the direction that is opposite to the dominant direction of heat flow. ii. In semi-solid freezing, solidification depends on the growth of preformed ice crystals and their fusion with each other.

[0093] Fig.12 :The versatility of semi-solid freeze casting for different material systems: from a variety of common biomaterials (natural macromolecular solutions, synthetic polymer emulsions ( Figure 7 ) and ceramic particles) with isotropic uniform porous structures; (A1 and B1) 3D reconstructions of the scaffolds based on micro-CT scanning. Pseudo-color analysis of the cross-section of the scaffolds shows that (A2) the semi-solid freeze casting forms a uniform structure, while (B2) the conventional freeze casting forms multiple small-sized domains with different defined orientations.

[0094] Fig.14 :(A) Compression modulus of PEG-based WPU scaffolds in dry and wet conditions. (B) Compression-rebound photos of these scaffolds in wet conditions. Sample size: 1×1×1 cm 3 (C) Water contact angle of WPU films based on PEG and PCL. n=3.

[0095] Fig.16 :(A) F-actin staining (rhodamine-labeled phalloidin) of cells cultured in the porous scaffold (PEG15-WPU) of the patch. (B) L929 cells cultured on the film on the top surface of the patch. (C) CCK-8 assay after 24 h of co-culture of cells with the degradation products of the patch. 1000×, 100×, and 10× indicate that the degradation solution was diluted 10 times, 100 times, and 1000 times, respectively. (D) Scratch assay of cells cultured on PEG15-WPU membranes or tissue culture polystyrene (TCP) plates, and the remaining scratch area was quantified using ImageJ software. (EG) In the presence or absence of LPS stimulation (300 ng mL -1 ) were used to measure the secretion of inflammatory factors by RAW264.7 macrophages on TCP plates, in PEG15-WPU scaffolds, and in dECM scaffolds, including (E) TNF-α and IL-10 determined by ELISA and (F) NO detection. (G) RT-qPCR detection of iNOS and Arg-1 in macrophages after LPS stimulation. GAPDH was used as an internal control, and the gene expression level of macrophages cultured on TCP plates without LPS stimulation was used as a control to calculate the relative mRNA expression. Data are expressed as mean ± SD (n = 3), and (DG) were analyzed by one-way ANOVA, *P < 0.05, **P < 0.01, ***P < 0.001.

[0096] Fig.17: (A) H&E stained sections of implanted PEG15-WPU scaffolds and surrounding skin tissue. Red asterisks indicate implanted scaffolds, and yellow arrows indicate residual scaffold fragments. Shortly after implantation, cell infiltration and tissue growth were observed throughout the scaffold, indicating that the material had completely integrated with the tissue, and the scaffold could be completely degraded in vivo after approximately two months. (B) Histopathological analysis of major organs showed that rats implanted with scaffolds had no significant differences from healthy rats within 8 weeks after implantation.

[0097] Fig. 22 : (A) Macroscopic photographs of defects 12 weeks after different treatments. Dashed circles indicate raised ridge scars. Histological evaluation of regenerated mucosal matrix: (B) Masson trichrome staining and (C) fiber orientation analysis and (D) corresponding orientation distribution curves.

[0098] Fig.23 : There are more hair follicles and glands in the oral mucosa of small animals, and the epidermis is thinner than that of human mucosa. Also, like the skin, the mucosa is relatively separated from the muscle layer, with a unique fascia layer (panniculuscarnosus layer) in between, so the two can slide relative to each other, allowing wounds to heal by contraction. In contrast, the structure of pig mucosa is more similar to that of human mucosa, both are hairless, and are closely connected to muscle tissue and cannot slide relative to each other.

[0099] Example 1

[0100] Materials and methods

[0101] Semi-solid freeze casting process

[0102] First, the semi-solid freeze casting process of the present invention utilizes a dynamic freezing method to prepare a "porridge-like" semi-solid ice slurry. First, the liquid material is precooled to 2-4°C and left overnight. The precooled liquid material is then transferred to a mechanical stirrer, and liquid nitrogen (LN2) is gradually added while the liquid material is continuously stirred during the initial freezing stage. The volume ratio of LN2 to liquid material is approximately 2:1-3:1. LN2 should be added relatively slowly (e.g., 0.5-10 mL / min) to avoid the formation of large ice cubes, thereby avoiding damage to the uniformity of the semi-solid ice slurry. The present invention found that the stirring rate may affect the final porous structure of the scaffold, so during the dynamic freezing process, the present invention divides the stirring into at least two stages, wherein the specific conditions of the first stirring stage include stirring at a first stirring rate of 200-300 rpm for a time of t1 (2-5 min), adding a first volume of liquid nitrogen during the first stirring period, and the first volume includes 30%-45% of the volume of the liquid nitrogen; the specific conditions of the second stirring stage include stirring at a second stirring rate of 400-600 rpm for a time of t2 (5-8 min), adding a second volume of liquid nitrogen during the second stirring period, and the second volume includes 55%-70% of the volume of the liquid nitrogen. The continuous stirring of the present invention not only helps to homogenize the entire system, but also prevents the formation of large ice crystals, that is, even if large ice crystals are formed in some areas of the system, the continuous stirring of the present invention can break the large ice crystals into small ice crystals, thereby ensuring that the small ice crystals are evenly distributed in the formed semi-solid ice slurry. Specifically, the present invention initially stirs the liquid material for t1 time at a lower first stirring rate, so that the temperature of the liquid material can gradually approach the temperature of liquid nitrogen at a suitable speed, and ice crystals are formed under the action of liquid nitrogen; and the higher second stirring rate can better stir the liquid material with higher viscosity due to the increase in the generation of solid phase ice crystals (or the transition state of the liquid material to the semi-solid ice slurry). In addition, the second stirring rate can further ensure the homogenization of the system and the uniform dispersion of heat, thereby ensuring the uniform generation and dispersion of ice crystals. Then, the second stirring rate is maintained for t2 time, which can ensure that the liquid material is controlled and maintained in a semi-solid ice slurry state as a whole and bubbles are further introduced, so that the generated semi-solid ice slurry forms a three-phase coexistence structure in which nearly spherical ice crystals (solid state) and bubbles are uniformly dispersed in the liquid phase matrix, which provides a basis for the subsequent formation of a uniform porous structure. In addition, the porosity of the porous scaffold generated in the above-mentioned first stirring stage and the second stirring stage can be maintained at 60-80%.

[0103] Optionally, the stirring of the present invention may further include a third stirring stage, wherein the third stirring stage includes adding an additional third volume of liquid nitrogen to the liquid material and stirring at a third stirring rate for a time of t3, wherein the third stirring rate includes 900-1200 rpm, the t3 time includes 5-8 min, and the third volume includes 45%-55% of the total volume of the liquid nitrogen added in the first stirring stage and the second stirring stage. The present invention finds that when the stirring rate of the liquid material exceeds 900-1200 rpm (i.e., three stages of stirring are performed), the ice slurry will incorporate more bubbles, thereby resulting in a higher porosity of the obtained scaffold, for example, 70-95% ( Fig.24 A). That is, the present invention can further adjust the porosity to achieve the desired porosity by adding a third stirring stage. The huge temperature difference between LN2 and the liquid material, coupled with the shearing effect, promotes the formation of fine ice crystals, thereby forming a semi-solid ice slurry, namely "porridge-like ice". Fig.24 In A1, the liquid material is 14wt% polyurethane emulsion (the volume of liquid nitrogen is 3 times that of the liquid material), the first stirring stage: 250rpm, 3min (40% of the volume of liquid nitrogen), the second stirring stage: 600rpm, 6min (60% of the volume of liquid nitrogen); Fig.24 In A2, the liquid material is 14wt% polyurethane emulsion (the volume of liquid nitrogen is 3 times that of the liquid material), the first stirring stage: 250rpm, 3min (40% of the volume of liquid nitrogen), the second stirring stage: 600rpm, 6min (60% of the volume of liquid nitrogen), the third stirring stage: 1100rpm, 6min (additional 50% of the volume of liquid nitrogen).

[0104] The semi-solid ice slurry was then quickly transferred to a designated mold and placed in a -20°C freezer for at least 12 hours for secondary freezing. The sample was then freeze-dried to form a porous scaffold after ice crystals sublimated.

[0105] This example tests the scalability of the semi-solid freeze casting process. The results show that the present invention can prepare large-sized porous scaffolds of various shapes, such as large-area porous sheets (20×38×0.3 cm 3 ), large porous blocks (4×3×3cm 3 ) and irregular shaped (star-shaped, crown-shaped, heart-shaped) scaffolds, and all of the above porous scaffolds have isotropic uniform porous structures. For these larger samples, a floor-standing large-capacity freeze dryer (SCIENTZ-200F / A, Ningbo Xinzhi) was used for freeze drying for 48-96 hours depending on the sample size.

[0106] This example also tests the semi-solid freeze casting process provided by the present invention with different materials:

[0107] (i) 10–40 wt% WPU emulsion ( Fig.24 A1 shows a polyurethane emulsion with a liquid material of 14 wt% (the volume of liquid nitrogen is 3 times that of the liquid material), the first stirring stage: 250 rpm, 3 min (40% of the volume of liquid nitrogen), the second stirring stage: 600 rpm, 6 min (60% of the volume of liquid nitrogen);

[0108] (ii) 0.5–3 wt% hyaluronic acid solution ( Fig.12 The liquid material is shown to be a 1.5wt% hyaluronic acid solution (Mw 200000-400000; Macklin, Shanghai, China) (the volume of liquid nitrogen is 3 times that of the liquid material), the first stirring stage: 300rpm, 2min (45% of the volume of liquid nitrogen), the second stirring stage: 600rpm, 8min (55% of the volume of liquid nitrogen));

[0109] (iii) 1.5–3 wt% sodium alginate solution ( Fig.12 The liquid material is shown as 2 wt % sodium alginate solution (Aladdin, Shanghai, China) (the volume of liquid nitrogen is 3 times that of the liquid material), the first stirring stage: 300 rpm, 4 min (35% of the volume of liquid nitrogen), the second stirring stage: 550 rpm, 7 min (65% of the volume of liquid nitrogen);

[0110] (iv) 14–25 wt% hydroxyapatite suspension ( Fig.12 The liquid material is shown to be 14wt% hydroxyapatite (particle size 60-80nm, 2wt% polyvinyl alcohol (Mw~67,000) as a binder, 0.5wt% ammonium polyacrylate as a dispersant, all provided by Macklin) (the volume of liquid nitrogen is twice that of the liquid material), the first stirring stage: 200rpm, 5min (40% of the volume of liquid nitrogen), the second stirring stage: 400rpm, 5min (60% of the volume of liquid nitrogen)).

[0111] For micro-CT characterization, iohexol (Macklin) was added at an appropriate concentration (65 mg mL-1) as an X-ray contrast agent. The porous scaffolds formed by the above materials can be used for tissue regeneration. Fig.26 It is also shown that the pore size of the porous scaffold decreases with the increase of the solid content of the WPU emulsion. In other words, the porous scaffold with the desired pore size can be controlled by controlling the concentration of the liquid material.

[0112] This example also evaluated an indirect dynamic freezing method, which involved placing a container containing a liquid suspension in an LN2-ethanol ice bath (-80°C). The suspension was stirred at 300 rpm for about 40 minutes until a semi-solid ice slurry was formed. After freeze drying, the final porous scaffold morphology showed that the sublimated ice crystals were larger plates rather than small equiaxed grains ( Fig.24 B).

[0113] Characterizing the Semi-Solid Freeze Casting Process

[0114] The microstructure of the semi-solid WPU ice slurry was observed under an inverted microscope at 0°C. After freezing at -20°C for 12 hours, the ice slurry was moved to LN2 and divided into two parts to expose the cross section. Subsequently, the morphology of the ice crystals in the frozen state (-190°C) was observed using a SEM (SU3500, Hitachi, Japan) equipped with a cryo-SEM preparation system and EDS. The shear thinning behavior of the semi-solid WPU slurry was confirmed by measuring its viscosity as a function of shear rate from 1 to 100s-1 at 0°C using a modular compact rheometer (MCR102, Anton Paar, Germany). In comparison, the viscosity of the fully liquid WPU emulsion and water was also measured using the same method.

[0115] After the freeze-drying process, the porous structure of the scaffolds was investigated using field emission SEM (Apreo S HiVoc, FEI, USA) and micro-CT (VivaCT80, SCANCO Medical AG, Switzerland). For conventional SEM, the samples were gold sputtered for 120 seconds at a constant current of 30 mA and observed at an accelerating voltage of 5 kV. For cyro-SEM, the samples were gold sputtered for 60 seconds at a constant current of 20 mA and observed at an accelerating voltage of 10 kV (15 kV for EDS). The porosity of the scaffolds was analyzed by orientation on the micro-CT images using an open source plugin for ImageJ software (http: / / bigwww.epfl.ch / demo / orientation / ).

[0116] By using ProCAST 2021.5 software for finite element simulation, the effect of nucleation density on ice crystal morphology can be intuitively seen. In short, the ice mold was simplified to a cubic model (5×5×5cm 3), including 1,380 surface mesh elements and 5,964 volume mesh elements. Water with an initial temperature of 4°C was used as the simulation object and poured into the ice mold. The ambient temperature was set to -20°C, and the heat transfer constant of the inner and outer walls was set to 500W(m2-K)-1. The volume nucleation density gradients were set to 107m-3, 108m-3, 109m-3, 1011m-3 and 1013m-3, respectively, with an average supercooling of 1.5K for volume nucleation. During the freezing process, the ice crystal growth and temperature field were recorded.

[0117] Synthetic WPU

[0118] In the preparation of two PEG-based WPU emulsions ( Fig.13 A), PCL (Mw = 2,000, Dow Chemical, USA) and PEG (Mw = 1,450, Dow Chemical) were first added to the reaction bottle in a molar ratio of 85:15 or 75:25. Then dehydrated at 95°C for two hours and cooled to room temperature. Under a nitrogen environment, LDI (Nantong Dahong Chemical Industry Co., Ltd., China) was added and reacted at 80°C for 1.5 hours. Next, 1,3-propylene glycol (PDO) was added for chain extension reaction at 70°C for 1 hour. The prepolymer was then poured into an L-lysine aqueous solution (TCI Shanghai) for emulsification, and sodium hydroxide was added to adjust the pH to 7.4. The final product was achieved by stirring the emulsion at high speed (1,500 rpm) at room temperature for two hours to allow the emulsion to reach equilibrium, and then reducing the speed to 570 rpm. PEG-based WPU includes such as Fig. 27 In some embodiments, PEG-based WPUs are prepared according to the preparation methods summarized in Table 1.

[0119] Table 1

[0120]

[0121] 16.52 g of PCL (Mw = 1,000, Dow Chemical, USA) was dehydrated at 95°C for two hours in a three-necked flask and then cooled to about 60°C to prepare a PCL-WPU emulsion ( Fig.13B). 13.53 g of isophorone diisocyanate (IPDI, Covestro Polymer, Shanghai, China) and organic bismuth (used as a catalyst) were added and prepolymerized at 85°C for one hour. The temperature was then reduced to about 60°C, and 1.83 g of 2,2-bis(hydroxymethyl)propionic acid (DMPA, Aladdin, Shanghai, China) was added, followed by a chain extension reaction at 85°C for one hour. The prepolymer was then cooled to 45°C, and 1.378 g of triethylamine (TEA, Colon Chemical, Chengdu, China) was added to neutralize the hydroxyl groups for 30 minutes. The reactor was then moved to a water bath, and 4.445 g of IPDI and 10.432 g of polycaprolactone triol (Capa3091, Pastto Chemical, Shenzhen, China) were added in sequence and stirred at 1200 rpm for 15 minutes. After homogenization, the stirring speed was reduced to 800 rpm, and deionized water was slowly added. When the viscosity of the reaction system reached the critical point, the stirring speed was rapidly increased to 2,000 rpm to achieve phase inversion. Emulsification was performed at a stirring speed of 2,000 rpm in an ice bath for 40 minutes. Finally, the temperature was raised to 45 °C and the microemulsification reaction was initiated for 3 hours to form a PCL-WPU emulsion.

[0122] Preparation and characterization of WPU multilayer patches

[0123] As described above, PEG15-WPU or PEG25-WPU solution was used to make porous scaffolds by semi-solid freeze casting. Subsequently, the PCL-WPU emulsion was concentrated by vacuum distillation at 45°C to a solid content of about 50-70% (e.g., 60%). It was then evenly coated on the surface of the prepared scaffold and then dried in an oven at 40-80°C (e.g., 50°C) for 6 hours to form an asymmetric WPU patch. The concentrated emulsion had a paste-like consistency and high viscosity to avoid infiltration into the porous scaffold. The mechanical properties of the patch in both dry and wet states were evaluated using a universal material testing machine (HZ-1004, Dongguan Lixian Instrument Scientific Co. Ltd., China). It should be understood that other common biodegradable biomaterials (e.g., PLGA (polylactic acid-co-glycolic acid), PCL (polycaprolactone)) can also be selected to make the top film of the patch to provide mechanical properties for the porous scaffold. In some embodiments, natural materials such as chitosan can be used to adjust the modulus of the top film. The tensile test was performed at a speed of 20 mm per minute, and the compression test was performed at a speed of 10 mm per minute, with a maximum compression deformation of 70%. The water contact angles of the three WPU films were measured on a DSA-100 goniometer (Krüss GmbH, Hamburg, Germany) using 3 μL of distilled deionized water. The multilayer structure of the patch in both dry and wet states was observed using field emission scanning electron microscopy (SEM) and scanning electron microscopy (CLSM) (Nikon N-SIM, Japan).

[0124] Cell experiments

[0125] L929 cells (Chinese Academy of Sciences Cell Bank, #GNM28), HUVECs (Procell Life Science & Technology Co., Ltd., Wuhan, China, #CL-0122) and RAW264.7 macrophages (Chinese Academy of Sciences Cell Bank, #TCM13) were cultured in high-glucose DMEM (Gibco) supplemented with 10% fetal bovine serum (Hyclone) (L929 cells used 10% horse serum (Gibco)) and 1% penicillin / streptomycin (Gibco). The cultures were maintained under standard conditions (37°C, 5% CO2) and the culture medium was replaced every two days. The samples were sterilized with gamma rays at a dose of 15 kGy and then rehydrated with DMEM overnight before cell inoculation.

[0126] For morphological analysis, cells were seeded on one side of the porous scaffold of the patch at a density of 1×106 cells per scaffold in a 24-well plate. PEG15-WPU and PEG25-WPU scaffolds were tested. After 3, 7, and 11 days of culture, cells were fixed with 4% paraformaldehyde for 30 minutes, and then the cell membrane was permeabilized with 0.5% Triton X-100 for 10 minutes. F-actin and cell nuclei were then stained with rhodamine phalloidin (Solarbio Science & Technology Co., Ltd., Beijing, China, #CA1610) and DAPI (Solarbio, #C0065), respectively. Fluorescence images were captured by CLSM.

[0127] In the biotoxicity test of the degradation products, 0.2 g of the patch was completely degraded in 10 mL of 1 M NaOH solution. It was then neutralized to pH 7.4 with HCL solution and sterilized with a 0.22-μm filter. The prepared degradation solution was diluted 10-fold, 100-fold, and 1000-fold with serum-containing cell culture medium. The cells were seeded in 48-well plates (8 × 10 4 Cells were cultured in 4% paraformaldehyde (40% cell / well) until the cell confluence reached 80%, and then cultured for another 24 hours with medium containing different concentrations of degradation products. Cell viability was then determined using the CCK-8 method (Beyotime Biotech, Inc., Shanghai, China, #C0038).

[0128] In the scratch test, 1.5 mL of 14 wt% PEG15-WPU emulsion was added to each well of a 6-well plate and then dried at 50 °C to form a coating of the WPU film. After sterilization, cells were seeded into 6-well plates with or without WPU film (5 × 10 cells per well). 5 Cells were cultured in complete DMEM until a monolayer of cells was formed. Scratches were made with a 1-mL pipette tip. Floating cells were washed three times and the remaining cells were cultured with low serum (2%) DMEM to inhibit proliferation. Cell migration was photographed with an inverted microscope (Olympus CKX41, Japan) at designated time points (12, 24, and 36 hours), and the scratch area was measured using ImageJ 1.53e software.

[0129] For macrophage polarization analysis, RAW264.7 cells were cultured at 5 × 10 5Cells were seeded at a density of 100 cells / sample (cells / well) on the patch, the porous side of the dECM-derived scaffold, and a 6-well plate (as a control). After allowing the cells to adhere for 24 hours, the medium was replaced with complete medium containing LPS (300 ng mL-1) or without LPS and cultured for another 24 hours. The supernatant was then collected and tested for ELISA (Solarbio, TNF-α, #SEKM-0034 and IL-10, #SEKM-0010) and NO release (Beyotime, #S0021S) according to the manufacturer's instructions. The cells on the collection plate were seeded with patches or scaffolds and control cells for RT-qPCR analysis.

[0130] Rat subcutaneous implantation model

[0131] Female SD rats (180-200 grams; Dashuo Biotechnology Co. Ltd., Chengdu, China) were used to evaluate in vivo tissue compatibility and degradation behavior. The rats were anesthetized with 50-80 mg kg-1 of pentobarbital, and then the PEG15-WPU stents were implanted in subcutaneous pockets on the backs of the rats. At predetermined time points (2, 4, 6, and 8 weeks after implantation), the rats were euthanized. The remaining stents and surrounding skin tissues were then collected for H&E staining. In addition, the main organs of the rats were collected 8 weeks after surgery to evaluate systemic toxicity compared with healthy rats.

[0132] Pig oral mucosal defect repair model

[0133] Female pigs weighing 20-25 kg (Guangxi Mini Bama Xiang pigs, domestic pigs (sus scorfa domestica), Sichuan University Experimental Animal Center) were fasted for 12 hours and then injected intramuscularly (Virbac, France) was used for anesthesia (initial dose of 1.8 mL, followed by up to four injections of 0.7 mL each), and the operation time was one hour. The animals were fixed in a prone position, and the oral mucosa was disinfected with betadine. A large buccal mucosal defect was created by resecting the full-thickness mucosa and submucosa (area 2.5×2.5 cm2, depth approximately 4 mm). After hemostasis, vaseline gauze, dECM scaffolds, and WPU multilayer patches were implanted to fill the defect bed. Analgesics (ibuprofen, SK&F, China) were administered for three days after surgery. The defect site was photographed every 7 days, and tissue samples were collected at designated time points (14, 28, and 84 days after surgery). For RNA-seq and RT-qPCR analysis, specimens were collected from anesthetized animals at the defect site using an 8 mm biopsy puncture needle. Immediately after euthanasia, the buccal mucosa was separated along the upper and lower jaws to measure the mucosal width (such as 1.5 mm) using a C-type Shore durometer. Fig. 20 The defect site and surrounding tissues were then collected for histological evaluation.

[0134] Histological analysis

[0135] The collected tissue samples were fixed in 4% paraformaldehyde for 48 hours and then rinsed with 1X PBS. The tissues were dehydrated, washed, embedded in paraffin, and then cut into 5 μm thick sections for H&E and Masson trichrome staining. Finally, images were collected using an automated digital slide scanner (Pannoramic MIDI, 3DHISTECH Ltd., Hungary). Immunohistochemistry was performed according to standard protocols. After treatment with antigen retrieval buffer, sections were blocked with 3% BSA for 1 hour at room temperature to prevent nonspecific binding. After rinsing with PBS, sections were incubated with primary antibodies at 4°C overnight. Sections were then rinsed with PBS and incubated with fluorescently labeled secondary antibodies for 50 minutes and then incubated with autofluorescence quenching reagents for 5 minutes. Cell nuclei were stained with DAPI, and fluorescence images were captured using a confocal microscope. Immunofluorescence images were semiquantitatively analyzed using ImageJ software and expressed as percentage of positive area or number of positive cells per high-power field (HPF, 40× or 60×). Based on Masson-stained sections, fiber orientation analysis was performed using an open source ImageJ plug-in (http: / / bigwww.epfl.ch / demo / orientation / ).

[0136] RT-qPCR analysis

[0137] According to the manufacturer's instructions (Invitrogen), Reagents are used to extract RNA from cultured cells or oral mucosal tissues. After extracting mRNA, the RNA is extracted using a Reverse transcription was performed using the Q RT SuperMix Kit (Vazyme) and amplification was performed using PCR (ABI 7300, Applied Biosystems, USA) using ChamQ SYBR Color qPCR Master Mix (2X) (Vazyme). Primer sequences are shown in Table 2. Gene expression data were expressed using GAPDH (cell studies) or ACTIN (animal studies) as internal reference genes at 2 -ΔΔCt Normalization of law.

[0138] Table 2

[0139]

[0140]

[0141] RNA-seq analysis

[0142] RNA extraction:The ELISA kit was used according to the manufacturer's instructions (Invitrogen, Carlsbad, USA). Total RNA was extracted from tissues using 50 μg / ml reagents and genomic DNA was removed using DNase I (TaKaRa, Osaka, Japan). RNA quality was then determined using a 2100 Bioanalyzer (Agilent) and quantified using ND-2000 (NanoDrop Technologies Inc., USA). Only high-quality RNA samples (OD 260 / OD 280 =1.8-2.2, OD 260 / OD 230 ≥2.0, RIN ≥6.5, 28S:18S ≥1.0, >1μg) were used to construct sequencing libraries.

[0143] Library preparation and Illumina HiSeq XTen sequencing: 1 μg of total RNA was used and the sequence was analyzed using the TruSeq protocol of Illumina (San Diego, USA). TM RNA-seq transcriptome libraries were prepared using an RNA sample preparation kit. Briefly, first, messenger RNA was isolated using oligo(dT) beads according to the polyA selection method and then fragmented using fragmentation buffer. Double-stranded cDNA was then synthesized using the SuperScript Double-Stranded cDNA Synthesis Kit (Invitrogen) and random hexamer primers (Illumina). The synthesized cDNA was then end-repaired, phosphorylated, and "A" base added according to Illumina's library construction protocol. 300 bp cDNA target fragments were screened on 2% Low Range Ultra agarose and then PCR amplified using Phusion DNA Polymerase (NEB) for 15 PCR cycles. After quantification by TBS380, the paired-end RNA-seq sequencing library was sequenced (2×150 bp read length) using an Illumina HiSeq xten / NovaSeq6000 sequencer.

[0144] Quality control and read mapping: The raw paired-end reads were trimmed and quality controlled using fastp (https: / / github.com / OpenGene / fastp) with default parameters. The clean reads were then aligned to the reference genome in orientation mode using HISAT2 (http: / / ccb.jhu.edu / software / hisat2 / index.shtml) software. The matched reads for each sample were assembled by StringTie (https: / / ccb.jhu.edu / software / stringtie / ) using a reference-based approach.

[0145] Differential expression analysis and functional enrichment: To determine the DEGs (differentially expressed genes) between two different samples, the expression level of each transcript was calculated according to the transcripts per million reads (TPM) method. RSEM (http: / / deweylab.biostat.wisc.edu / rsem / ) was used to quantify gene abundance. Basically, differential expression analysis was performed using DESeq2, and DEGs with |log2(fold change)|≥1 and P-value≤0.05 were considered as significantly differentially expressed genes. In addition, functional enrichment analysis including GO (http: / / www.geneontology.org) and KEGG (http: / / www.genome.jp / kegg / ) was performed to determine which DEGs were significantly enriched in GO terms and metabolic pathways at P-adjust≤0.05 compared with the whole transcriptome background. GO functional enrichment and KEGG pathway analysis were performed by Goatools (https: / / github.com / tanghaibao / Goatools) and KOBAS (http: / / kobas.cbi.pku.edu.cn / home.do).

[0146] The present invention provides a novel semi-solid freeze-casting technology that can be used to mass-produce three-dimensional porous scaffolds with controllable isotropic pore structures, which is helpful for the practical application of scaffolds in large-scale tissue regeneration. The present invention transforms the starting frozen material from a liquid material into a semi-solid ice slurry, realizing a "semi-solid phase transition" in the freezing of an aqueous material system. According to characterization, this transformation is intended to introduce prefabricated primary ice nuclei to promote the final frozen grain structure to evolve from columnar crystals to equiaxed crystals, and finally sublimates the ice crystals to leave a uniform porous structure. The semi-solid freeze-casting method of the present invention is widely used and is applicable to a wide range of material systems, such as polymer emulsions, macromolecular solutions, and inorganic slurries.

[0147] Subsequently, the present invention uses semi-solid freeze casting technology to manufacture porous scaffolds, and takes relatively complex oral mucosal defects as a representative (defect depth exceeding 4mm, moist, dynamic oral environment with multiple bacteria), and verifies the excellent performance of the isotropic porous scaffolds prepared by the present invention in reconstructing a wide range of mucosal (and skin) defects. Specifically, the present invention uses biodegradable waterborne polyurethane (WPU) to make large-sized isotropic porous scaffolds, and adds a barrier film on its surface to form a double-layer patch of biomimetic mucosa ( Figure 1 ); and further evaluate the effect of the patch as an intraoral repair material for large-area defect healing. The present invention uses a pig model ( Fig.23) showed that the patch significantly changed the healing trajectory that relied on contraction, promoted nearly scarless mucosal reconstruction, and thus alleviated the problem of limited mouth opening. Figure 1 As shown in the results, it was found that the basic mechanism of the WPU stent prepared by the present invention for treating defects involves congenital (CD86 + M1 macrophages) and adaptive (CD3 + The results showed that the semisolid freeze-casting technique can be used to fabricate porous scaffolds for regenerative medicine.

[0148] Embodiment 1:

[0149] Semi-solid freeze casting design

[0150] In traditional freeze casting, the liquid suspension is usually placed on the partition of a refrigerator or freeze dryer for constant temperature freezing, and then freeze-drying to form a porous structure. This process is called random or non-directional freezing. In theory, the nucleation and growth of ice are random in any direction, thus forming an isotropic porous structure. However, the constant temperature freezing in the existing technology can generate a uniform porous structure when preparing millimeter-sized samples, but once the process is scaled up to produce large-sized samples above the centimeter scale, it faces great challenges (for details on the scale-up process of the traditional freezing process, see Figure 7 ). The result is often structural heterogeneity, which is manifested in the appearance of numerous short-range ordered small-sized orientation domains in a large-sized sample, highlighting the poor scalability of ice-templated porous materials and the difficulty in preparing large-scale isotropic uniform porous structures.

[0151] This embodiment proposes a semi-solid freeze casting method, which includes three key steps: preparation of semi-solid ice slurry, molding freezing, and freeze drying. Next, this embodiment takes biodegradable waterborne polyurethane (WPU) as an example to demonstrate the preparation process of a porous scaffold based on a semi-solid freeze casting method. The reason why biodegradable polyurethane (PU) is used in this embodiment is that polyurethane is an important biomedical polymer with excellent biocompatibility, flexible molecular structure design, and adjustable physical and chemical properties. It should be understood by those skilled in the art that other biocompatible polymer materials suitable for simulating extracellular matrix can also be used.

[0152] The initial and key step in semi-solid freeze casting is the "semi-solid phase transition" from a liquid aqueous suspension, emulsion or solution to an ice slurry. This is achieved by vigorously stirring the WPU emulsion during dynamic cooling and freezing it in combination with liquid nitrogen. The resulting WPU ice slurry can be formed into three-dimensional shapes ("SCU" and a flower) by syringe or extrusion and retains its shape even after cutting ( Figure 2 A). The obtained semi-solid ice slurry has the characteristics of shear-thinning non-Newtonian fluid, while WPU emulsion or pure water behaves as a Newtonian fluid with approximately constant viscosity ( Figure 2 B). In essence, the semi-solid ice slurry prepared by the present invention (taking WPU ice slurry as an example) is a semi-solid substance that has both liquid-like fluidity and solid stability. In addition, under an optical microscope, it is observed that the semi-solid ice slurry is a solid-liquid-gas three-phase mixture, in which a large number of nearly spherical primary ice crystals and bubbles are suspended and dispersed in a semi-frozen liquid matrix ( Figure 2 B).

[0153] After that, the semi-solid WPU ice slurry was transferred to a specific mold and frozen at -20°C to completely solidify and harden. The microstructure of the frozen sample was directly observed using a cryo-scanning electron microscope (cryo-SEM). During the initial ice slurry preparation stage, a large number of bubbles were mixed into the ice slurry. Therefore, some bubbles were still retained after further freezing and solidification, resulting in the formation of "porous ice" ( Figure 2 C). Combined with energy dispersive spectroscopy (EDS), it can be observed in high-magnification images that the ice crystals in the frozen WPU ice slurry are spherical and equiaxed, and the gaps between the ice crystals are squeezed and aggregated polymers ( Figure 2 C. Figure 8 This observation reflects the basic principle of ice templates, that is, the raw material components (such as polymer molecules, etc.) in the suspension / solution are repelled by ice crystals during solidification and compressed and gathered in the gaps between ice crystals. The results of morphological and compositional analysis show that the frozen ice slurry presents a polycrystalline structure, and the ice crystals are roughly equiaxed.

[0154] Finally, the sublimation of ice crystals produced a porous structure. Large-area porous WPU thin layers were prepared as components of multilayer patches ( Figure 2 D). The area of ​​the porous thin layer can be enlarged to hundreds of square centimeters (in this case, freeze drying can be carried out by a floor-standing large-capacity freeze dryer) ( Figure 2 D). The flow properties of the semi-solid ice slurry facilitate the shaping of the final scaffold into a variety of shapes, including large porous blocks and other irregular shapes ( Figure 2E). All the above-mentioned scaffolds of various shapes can maintain a uniform isotropic porous structure on a centimeter scale. In contrast, scaffolds obtained by traditional freeze casting process show uncontrollable structural heterogeneity ( Figure 2 D. Figure 2 E; Figure 7 and Fig. 9 In addition, this example also verifies the universal applicability of semi-solid freeze casting to different material systems (polymer emulsion, macromolecular solution and ceramic slurry) ( Fig.12 ). That is, the scalable semi-solid freeze casting technology of the present invention lays a solid foundation for the large-scale preparation of porous scaffolds and their practical application in tissue engineering.

[0155] The initial material of semi-solid freezing is a semi-solid slurry rich in primary (or nascent) ice particles, while the initial material of traditional freezing is a liquid material. This is the most significant difference between the two freezing methods. It is worth noting that due to the presence of prefabricated primary ice nuclei, semi-solid freezing has a higher initial nucleation site during the solidification process compared with traditional freezing. The inventors believe that this difference in nucleation sites may be the key factor that causes the two methods to form different solidification structures.

[0156] To verify this hypothesis, this example uses the finite element method to simulate the freezing process of an aqueous system in a constant temperature environment with different nucleation densities. The simulation results show that there is a gradient temperature field inside the frozen sample, with the temperature increasing from the mold wall to the center of the sample ( Fig.10 A); With the increase of nucleation density, the grain structure in the solidification structure tends to form nearly spherical equiaxed crystals ( Fig.10 B).

[0157] Under low nucleation density conditions ( Fig.10 Bi), heterogeneous nucleation initially occurs in a thin layer close to the container wall. As the freezing process continues, the crystallization latent heat at the solidification front is released backward through the frozen part and the container wall, forming a directional heat flow perpendicular to the container wall, which promotes the continuous growth of ice crystals in the opposite direction, thus forming centripetal columnar grains.

[0158] When the nucleation density increases to more than about 1×10 8 m -3 hour( Fig.10 Bii), the appearance of equiaxed grains was observed, which gradually replaced the columnar grains that continued to grow in the center of the frozen sample in the later stage of freezing. When the nucleation density is high enough, the entire sample can achieve a complete equiaxed crystal structure ( Fig.10 Biii).

[0159] This example also studies the solidification process through cooling curve analysis. Different inflection points and platforms record the key events in the phase change process ( Fig.11 A). In conventional freezing, when the temperature drops to supercooling, nucleation begins at point 1, accompanied by a sudden warming (points 1-2 represent the release of latent heat of phase change), followed by the continuous growth of ice crystals until complete solidification (points 2-3). This result, together with the simulation results, reveals the typical solidification process of liquid materials, which is based on heterogeneous nucleation on the container wall, followed by directional growth of ice crystals driven by temperature gradient ( Fig.11 Bi).

[0160] In contrast, in the case of semi-solid ice slurry freezing, solidification mainly depends on the growth of pre-existing primary ice nuclei (points 4-5), and the nucleation process is greatly weakened ( Fig.11 A). As is known to all, "nucleation" requires a higher degree of supercooling (i.e., a higher potential barrier) than "growth". Therefore, the present invention pre-establishes (can also be understood as "prefabrication") abundant primary ice nuclei in a semi-solid system, so that ice growth precedes nucleation. In other words, the present invention can separate the nucleation and growth of ice crystals. Nucleation occurs during the preparation of semi-solid ice slurry, and growth occurs during the solidification of ice slurry, ultimately achieving the transformation of the solidification structure from columnar ice crystals to equiaxial ice crystals ( Fig.11 Bii). A large number of prefabricated primary ice crystals inhibit the continued growth of any single grain in a specific direction, thereby alleviating the destructive effect of the gradient temperature field on the solidification structure.

[0161] Example 2

[0162] Preparation and characterization of multilayer patches

[0163] In this embodiment, a bionic multilayer patch was developed to test the wound healing and tissue regeneration performance of the porous scaffold prepared by the present invention and the corresponding patch. The patch includes: (a) a porous scaffold layer, which is composed of a porous scaffold formed by semi-solid freeze casting, which can serve as a temporary substitute for the submucosal ECM and promote tissue integration and repair; (b) a top surface dense layer (or top surface barrier layer), which simulates the sealing membrane of the epidermis and provides a barrier to the mechanical friction caused by oral movement, saliva and oral microorganisms. Both scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) confirmed that the patch (patch, or patch) showed a multilayer structure similar to that of natural oral mucosa in both dry and wet states ( Figure 2 F). The thickness of the porous support layer may be 2-10 mm, and the thickness of the top dense layer may be 0.2-0.8 mm.

[0164] Furthermore, this embodiment uses two different biodegradable waterborne polyurethanes (WPUs) to make an asymmetric patch: the porous scaffold layer uses a waterborne polyurethane based on polyethylene glycol (PEG) (PEG-WPU), and the top dense layer uses a waterborne polyurethane based on polycaprolactone (PCL) (PCL-WPU) (for the synthesis of PEG-WPU and PCL-WPU, see Fig.13 ). When synthesizing PEG-WPU, there are two concentrations of PEG in the soft segment: 15% (molar fraction, PEG15-WPU) and 25% (PEG25-WPU). In some embodiments, the concentration of PEG in the soft segment used to synthesize PEG-WPU (or the percentage of PEG in PEG-WPU to the content of WPU soft segment, the same below) includes 15%-30%. In some embodiments, in order to form a patch for tissues such as the oral cavity and epidermis, the concentration of PEG in the soft segment used to synthesize PEG-WPU may include 15%-20%. In some embodiments, in order to form a patch for tissues such as the brain, the concentration of PEG in the soft segment used to synthesize PEG-WPU may include 25%. It should be understood by those skilled in the art that a suitable PEG-WPU can be selected according to actual preparation requirements.

[0165] The results showed that the PEG15-WPU scaffold showed high modulus and low hydrophilicity compared with the PEG25-WPU scaffold ( Fig.14 ). The cytocompatibility and anti-inflammatory activity of the WPU patch were evaluated by in vitro studies using L929 fibroblasts, human umbilical vein endothelial cells (HUVECs), and RAW264.7 macrophages. First, after 3, 7, and 11 days of culture, the morphology of adherent cells within the porous scaffold of the patch composed of PEG15-WPU scaffold (with PCL-WPU film as the top surface dense layer, the thickness of the porous scaffold layer: 3.5 mm, and the thickness of the top surface dense layer: 0.6 mm) was observed using F-actin staining. On the 3rd day, most L929 cells showed a good spreading morphology within the PEG15-WPU scaffold and maintained an extended spindle shape in the following days ( Fig.16 A). The top film of the patch also promotes the adhesion and growth of L929 cells ( Fig.16 B). Similarly, HUVECs showed a good spreading morphology after 3 days of culture. On the 11th day, endothelial cells formed a three-dimensional cell network in the scaffold. In addition, the cell compatibility of the patch composed of PEG25-WPU scaffold (PCL-WPU film as the top surface dense layer, the thickness of the porous scaffold layer: 3.5mm, the thickness of the top surface dense layer: 0.6mm) was also good ( Fig.15 ).

[0166] The present invention selects a patch composed of a PEG15-WPU scaffold for subsequent experiments. Unless otherwise specified, the "patch" or "WPU patch" hereinafter refers to a patch sample with a PEG15-WPU scaffold as a porous scaffold layer and a PCL-WPU film as a top surface dense layer (thickness of the porous scaffold layer: 3.5 mm, thickness of the top surface dense layer: 0.6 mm). The tensile test shows that the modulus and strength of the patch are consistent with those of the natural buccal mucosa (Table 3).

[0167] Table 3 Tensile properties of WPU multilayer patches in wet and dry states (n=3).

[0168]

[0169] The cytotoxicity of the degradation products of the WPU patch was further studied. The patch was completely degraded in a strong alkaline solution, and L929 cells or HUVEC were co-cultured with different concentrations of the degradation products for 24 hours ( Fig.16 C). Cholecystokinin-8 (CCK-8) assay confirmed that the degradation products of the patch were not cytotoxic and the cell viability was over 85% at all tested concentrations.

[0170] Next, a scratch test was performed to evaluate the effect of WPU patch on cell migration. 24 hours after scratching, L929 cells showed faster migration speed on the PEG15-WPU membrane compared with the TCP group. At 36 hours, the cells on both sides of the scratch in the PEG15-WPU group merged with each other ( Fig.16 D). Similarly, for HUVECs, the remaining scratch area in the PEG15-WPU group was always smaller than that in the control group at all observation time points. These results suggest that the patch may accelerate cell migration.

[0171] In order to explore the immunomodulatory effect of the patch on macrophage polarization, in this example, RAW264.7 macrophages were cultured in the porous scaffold layer of the patch for 48 hours, with or without LPS stimulation for the last 24 hours. TCP plates and clinically used dECM scaffolds were used as controls. The secretion of TNF-α and IL-10 by the cells was measured by enzyme-linked immunosorbent assay (ELISA). Fig.16E). Under LPS stimulation, both dECM and PEG15-WPU scaffolds downregulated the secretion of the proinflammatory factor TNF-α, especially in the PEG15-WPU group; but the secretion of the anti-inflammatory factor IL-10 was significantly increased in the PEG15-WPU scaffold. The IL-10 / TNF-α ratio can show the polarization of macrophages, and the largest ratio was observed in the PEG15-WPU group, suggesting obvious M2 polarization. Under non-LPS stimulation conditions, although TNF-α and IL-10 expression were upregulated in dECM and PEG15-WPU scaffolds, no significant differences were observed in the IL-10 / TNF-α ratio between the three test groups. In addition, M1 macrophages induce the expression of iNOS and subsequently produce NO, which exacerbates inflammation and changes arginine metabolism. Therefore, this example performed NO detection and measured the gene expression of iNOS (M1 marker) and Arg-1 (M2 marker) using RT-qPCR to further determine the polarization state of macrophages. After LPS treatment, a significant decrease in NO generation was observed in the PEG15-WPU scaffolds compared with the other groups ( Fig.16 F), indicating that it plays an anti-inflammatory role by counteracting LPS-induced NO release. At the transcriptional level, as expected, the expression of M1 markers (iNOS ~75% TCP and ~64% dECM) was significantly reduced in the PEG15-WPU group, while the expression of Arg-1, which represents M2 polarization, was the highest ( Fig.16 G). This result is consistent with the results of ELISA. Therefore, in the LPS-induced in vitro inflammation model, PEG15-WPU scaffold can effectively promote the phenotypic transformation of macrophages from M1 to M2.

[0172] In terms of in vivo safety, the PEG15-WPU scaffold was evaluated using a rat subcutaneous implantation model. The results confirmed that the scaffold supported complete tissue growth and degraded approximately two months after implantation without causing significant damage to major organs ( Fig.17 ). These results indicate that the WPU patch has good biocompatibility and creates a pro-healing microenvironment for oral mucosal defects by promoting cell adhesion, migration, and immune response regulation.

[0173] Example 3

[0174] Efficacy of WPU patch in promoting scarless healing of large oral mucosal defects

[0175] Schematic diagram of the study on oral mucosal defect healing in a porcine model is shown in Figure 3 A. The buccal mucosa was resected by excision of approximately half of the unilateral buccal mucosa (size: 2.5 cm × 2.5 cm, ~4 mm thick) with submucosal lesions (see Fig.18), creating a large deep mucosal defect model that simulates the common large-area deep mucosal defects after surgical resection or facial trauma in clinical practice. The ability of the WPU patch to repair oral mucosal defects was verified compared with vaseline gauze (control group) and commercially available dECM scaffolds (see Fig.19 ). The buccal mucosa is a constantly moving part of the oral cavity and plays a vital role in physiological functions such as chewing, swallowing, and speech. Scar contracture is a common sequelae after severe mucosal trauma, posing a threat to the normal activities of the oral cavity and limiting the oral aperture, which directly affects the patient's quality of life and physical and mental health. A preliminary evaluation was performed to determine whether WPU patch treatment can reduce scar contracture and improve oral aperture. Gross observations 7 days after surgery showed that the control group had a large, bright red bleeding defect ( Figure 3 B). The defect gradually shrank, eventually forming a raised ridge scar on day 21. A similar healing trajectory was observed for defects treated with dECM, with defects shrinking and forming scars by day 28. In contrast, in the WPU patch group, the defect cavity was largely filled with new granulation tissue, with only minimal shrinkage on day 7, followed by rapid re-epithelialization. The regenerated mucosal tissue was relatively flat and smooth. These observations suggest two distinct healing processes: granulation tissue-based re-epithelialization in defects treated with the WPU patch and scar formation secondary to wound contraction in the other two groups. Thus, on day 28 after surgery, the mouth opening rate in pigs treated with the WPU patch was approximately 83%, while the mouth opening rates in pigs treated with the dECM and control groups were ~64% and ~58%, respectively ( Figure 3 C). Although the mouth opening was slightly affected in the WPU group compared with normal pigs (P = 0.0689), the mouth opening was significantly limited in the other groups (P = 0.0039 compared with the control group; P = 0.0198 compared with dECM). In addition, the hardness of the oral mucosa was significantly increased after the control group (P = 0.0238) and dECM treatment (P = 0.0014) compared with the WPU group ( Figure 3 D). These results indicate that WPU mesh can significantly reduce scarring and improve mouth opening in large, deep oral mucosal defects.

[0176] On day 28 after surgery, the regenerated oral mucosa of the different treatment groups was histologically evaluated and analyzed. Hematoxylin-eosin (H&E) staining revealed the typical histological morphology of scar contracture in both the control and dECM-treated defects, characterized by deformation of the submucosal connective tissue ( Figure 3E). The mucosal defect borders contract toward the center, and scarring eventually forms between the contracted borders, which also explains the limited mouth opening observed macroscopically from a microscopic perspective. When the defect heals primarily through border contraction rather than regeneration of the missing tissue, the loss of normal tissue in the original anatomical position leads to limited movement and scarring. In contrast, the WPU patch promotes the formation of new granulation tissue to fill the defect cavity ( Figure 3 E), effectively preventing wound contraction. As a result, the width of the newly formed tissue in the WPU group was approximately twice that of the other two groups (compared with the control group, P = 0.0039; compared with dECM, P = 0.0198; Figure 3 I).

[0177] The formation of early granulation tissue paves the way for subsequent wound epithelialization, a process in which epithelial cells migrate from the defect border to the center, effectively closing the wound by covering the granulation tissue with a continuous new epidermis. The results of immunohistochemical staining for keratin 19 showed that on day 28, the defects treated with the WPU patch were completely epithelialized, characterized by stratified squamous epithelium (including basal layer, granular layer, spinous layer, and stratum corneum). It can be seen that the epidermal papillae tightly connect the epidermis and the lamina propria ( Figure 3 F). In contrast, defects treated with dECM did not show complete epithelial stratification, although a thin epidermal layer was restored. The central area of ​​the control contracture defect was not completely covered by the new epithelium, indicating suboptimal wound epithelialization. Regeneration of epithelial tissue after injury depends on the proliferation of basal cells, where epidermal stem cells reside. Immunofluorescence staining for Ki-67, a nuclear protein marker that indicates proliferating cells, was used to examine the proliferation of basal cells ( Fig. 20 ). The defects treated with WPU patches had more actively proliferating basal cells at day 14, especially at the leading edge of epithelial migration, which facilitated epithelial confluence and regeneration. In contrast, in the other treatment groups, fewer proliferating basal cells were observed in the newly formed epidermis at the defect border, resulting in delayed epithelialization. + The number of basal cells is similar to that of normal tissue ( Fig.21 ), which is a prerequisite for epidermal self-renewal and homeostasis. However, the regenerated basal layer of the other two groups was significantly lacking in proliferating cells at 28 days.

[0178] In many organs, such as the dermis, conjunctiva, and endoneurium, collagen fibers within the matrix form a "basket-weave" structure, and abnormal collagen assembly is a characteristic of scar tissue, which appears as a parallel arrangement of fine fiber bundles. One of the main reasons for scar formation is the failure to reconstruct the physiological structure of the matrix. Therefore, the collagen fiber structure was analyzed to distinguish whether the newly formed matrix (including the lamina propria and submucosa) behaves as scar or physiological tissue after different treatments. Masson staining was used to identify collagen fibers, and Orientation J software (an open source ImageJ plugin) was used to analyze the orientation characteristics of collagen fibers. In both control and dECM-treated defects, collagen fibers in the lamina propria and submucosa were highly parallel to the epidermal plane ( Figure 3 G), showing a single-peak orientation distribution, indicating that the newly synthesized matrix is ​​anisotropic fibrous tissue, similar to scar ( Figure 3 J). In contrast, in defects treated with WPU patches, collagen fibers were randomly arranged, showing isotropic characteristics more similar to a woven structure. Therefore, the new matrix belongs to normal mucosal tissue rather than scar ( Figure 3 G. Figure 3 J). In addition, highly elongated fibroblasts were observed in the contraction defects treated with control and dECM ( Figure 3 H). The long axis of these elongated cells and the arrangement of collagen fibers are parallel to the macroscopic contraction direction. In contrast, the fibroblasts in the defects treated with WPU patches showed polygonal to spindle-shaped shapes with random axis directions. Therefore, the structural properties of the newly synthesized matrix in the defects treated with WPU patches are more similar to normal oral mucosa than scars. The results of this example confirm the "deformation field" theory of scar formation proposed by Yannas et al. According to this theory, contractile fibroblasts (mainly myofibroblasts) generate a centripetal stress field in the wound plane, driving wound contraction. At the same time, these fibroblasts are oriented parallel to the wound plane under the influence of this stress field. Subsequently, the collagen fibers synthesized by these oriented cells actually replicate the arrangement of the cells. Therefore, scar tissue characterized by highly oriented fibrous tissue is considered to be a derivative of wound contraction. This scar formation process has been observed in various organ injuries (including skin, peripheral nerves, conjunctival stroma and liver injuries) in adult mammals. This example is represented by oral mucosal defects to demonstrate this scar formation process secondary to contraction. The use of gauze and dECM scaffolds in clinical settings may lead to scar formation after severe oral mucosal defects. The results of this example show that the porous WPU patch guides the arrangement of growing cells and collagen assembly through its internal isotropic porous space, blocks the original directional arrangement of collagen fibers, and thus hinders wound contraction and inhibits scar formation.

[0179] To further support the above results, a three-month postoperative follow-up was performed in this example to evaluate the results of mucosal remodeling (see Fig. 22 ). In the control and dECM groups, macroscopic observations showed the presence of scarring and contraction, and histological examinations confirmed the formation of dense fibrotic scars due to the centripetal contraction of the deformed submucosal tissue. In contrast, no scars were visible in the defects treated with the WPU patch, and histological examinations showed interwoven collagen fibers, indicating that the matrix was very similar to normal mucosal tissue.

[0180] also, Fig.25 H&E staining analysis showed that the WPU patch (PEG15-WPU scaffold as the porous scaffold layer and PCL-WPU film as the top dense layer (thickness of the porous scaffold layer: 2 mm, thickness of the top dense layer: 0.4 mm)) can promote the healing of skin wounds: compared with the polyester foam scaffold (3M Tegaderm TM Compared with the control group (foam adhesive) and the control group (oil gauze), the WPU patch group significantly reduced inflammatory aggregation in the wound area of ​​the full-thickness skin defect rat model on the 7th day after surgery, and new tissue growth appeared at the material-tissue interface. On the 14th day after surgery, the inflammation was basically subsided and the WPU scaffold was partially degraded, while the commercially available polyester foam still stimulated tissue inflammation. These results indicate that the WPU patch can promote the regulation of the post-traumatic inflammatory microenvironment and guide tissue growth into the scaffold, thereby promoting wound healing.

[0181] Example 4

[0182] Regulation of innate and adaptive immune responses

[0183] The inflammatory response that occurs after tissue injury can initiate a series of regenerative processes. However, excessive inflammation can also damage functional cells and mask regenerative signals, leading to fibrotic scars. In order to explore the potential changes in the inflammatory response during defect healing, oral mucosal samples were collected in this example and evaluated 14 days after wound healing. During the overlapping period of inflammation and proliferation, maintaining a balance between pro-inflammatory and anti-inflammatory responses is essential to avoid wound deterioration and promote the formation of new tissue. Compared with the gross observations ( Figure 3 Consistent with B), hematoxylin-eosin (H&E) staining confirmed that the defects treated with WPU patches were undergoing an ongoing epithelialization process, characterized by the migration of epidermal tissue from the defect border to the center ( Figure 4a In contrast, the defects treated with dECM showed obvious unhealed areas, and the newly formed epithelium near the border was thin and fragile. There was almost no regeneration of epidermal tissue in the control group, accompanied by a large amount of inflammatory cell infiltration in the defect site. Immunofluorescence staining further revealed the presence of innate immune cells (CD68 + Macrophages) and adaptive immune cells (CD3+ The number of T cells Figure 4b The control group showed strong macrophage infiltration, with a predominant M1 polarization. Figure 4b This was demonstrated by the colocalization of CD68 and CD86 staining in B. In contrast, although the number of macrophages in the dECM group was slightly reduced, fewer M1 macrophages were found in defects treated with WPU patches. These cells were mainly scattered at the front end of the migrating epidermis (P<0.001 compared with the control group; P=0.0494 compared with dECM). Macrophages show heterogeneity and plasticity during inflammation and tissue repair, including multiple subpopulations (M1, M2a, M2b, and M2c types). M1 macrophages secrete various types of proinflammatory cytokines and amplify local inflammation. Their continued aggregation inhibits the proliferation of surrounding cells and delays healing. In addition, innate immunity represented by macrophages, as a core component of the immune system, can regulate T cell responses and adaptive immunity. The results of this example confirmed that compared with the control group (P=0.0149) and the dECM group (P=0.0337; Figure 4b C) Compared with the WPU patch treated defects, CD3 + The number of T cells was significantly reduced. T cells in the skin secrete the proinflammatory cytokine IL-17, which targets various cells (such as monocytes, endothelial cells, and keratinocytes) and induces the secretion of IL-1β, IL-6, and TNF-α, thereby exacerbating inflammation and fibrosis. The reduction in the number of T cells in the WPU patch group indicated a decrease in IL-17 secretion (compared with the control group, P = 0.0013; compared with dECM, P = 0.0233; Figure 4b D). Figure 4bAs shown in Figure E, the molecular dynamics of WPU patch-mediated immune regulation were explored by evaluating transcriptional gene expression through RNA sequencing (RNA-seq). KEGG analysis revealed a large number of DEGs involved in immune response, which were enriched in nine representative KEGG pathways, including cytokine-cytokine receptor interaction, IL-17 signaling pathway, and cell adhesion molecules. Hierarchical clustering of these inflammation-related DEGs in the heat map showed that ∼70% and ∼77% of the DEGs were significantly downregulated in WPU patch-treated defects compared with the control group and dECM group, respectively. Among them, two pathways (i.e., map04060 and map04668) were found to be associated with proinflammatory mediators produced by various types of immune cells, involving many genes that were downregulated in the defects treated with WPU patches, such as genes belonging to the CC chemokine subfamily (CCL2, CCL3, and CCL20), the CXC chemokine subfamily (CXCL8 and CXCL10), interleukins (IL-1β, IL-6, and IL-33), and the TNF superfamily (TNF-α). These genes are detailed in Table 4. In addition, three KEGG pathways involved in adaptive immunity (map04660, map04658, and map04659) were also significantly downregulated by WPU patches, including the downregulation of genes related to T cell receptor signaling (such as CD45, CD4, and CD3E) and the transcription factor AP-1 (FOS). This downregulation was accompanied by a reduction in IL-17 signaling (map04657; IL-17A, IL-17F, and IL-17C). Finally, WPU patching also led to the downregulation of three pathways related to inflammatory signal transduction (map04630, map04062, and map04514), especially the JAK-STAT signaling pathway, which is involved in a wide range of immune regulatory processes and is a potential target for inflammatory and fibrosis therapies.

[0184] Table 4 Full names and abbreviations of genes mentioned in the present invention

[0185]

[0186] RT-qPCR confirmed the expression of several key genes. Figure 4bAs shown in F, the expression of cytokine-related genes (such as IL-1β, IL-6, and CCL2) was downregulated in the WPU group. In addition, in the defects treated with WPU patches, the expression of genes indicating various immune cells (including macrophages (CD68), T cells (CD3E), and leukocytes (CD45)) was reduced, which also verified the findings of RNA-seq data and immunofluorescence results. In summary, these results provide convincing evidence for the immunomodulatory ability of the WPU patch. This ability is mainly manifested in the reduction of inflammatory cell infiltration and the extensive downregulation of pro-inflammatory gene expression. Therefore, the WPU patch may help create a favorable microenvironment for cell proliferation and subsequent tissue regeneration.

[0187] Broad activation of pro-healing gene expression: a catalyst for granulation and re-epithelialization

[0188] As a supplement to the inflammation analysis, this example also evaluated changes in signaling pathways related to repair and regeneration 14 days after surgery. Using gene ontology (GO) enrichment, DEGs were modularly analyzed and three major gene modules were obtained. Figure 5a As shown in the AC of the WPU group, these modules correspond to different biological functions, involving wound response, collagen matrix deposition, and epithelialization. These modules represent the most important molecular and cellular events related to tissue remodeling during the proliferation phase. Comparison between the WPU group and the control group revealed that 14 significantly changed GO pathways were enriched in the wound response module ( Figure 5a A). Approximately 72% of the genes in this module were upregulated after WPU patch treatment. These genes were mainly involved in processes such as skin barrier establishment (GO: 0061436; e.g. KRT1, TP63, KDF1, and GRHL3), skin development (GO: 0043588; e.g. WNT10A, SOX21, and ITGA3), and wound healing (GO: 0042060; e.g. WNT5A and SDC1). The wound response module was associated with 12 altered GO pathways compared to the dECM group, of which 61% of the genes were upregulated in the WPU group. These genes were related to skin development, wound healing, and regulation of wound response (GO: 1903034). Genes within this module were generally upregulated in defects treated with WPU patches, suggesting that WPU patches may be more beneficial in promoting wound healing compared to other treatment groups. During defect repair, the deposition of newly synthesized collagen matrix is ​​crucial, which provides the basis for angiogenesis and tissue recovery. In the collagen matrix deposition module, many significantly changed GO pathways were also found (e.g. Figure 5aAs shown in B, there were 7 pathways in the WPU group compared with the control group, and 15 pathways in the WPU group compared with the dECM group). These pathways were mainly involved in collagen-related biological processes, such as collagen biosynthesis (GO:0032964) and collagen fiber assembly (GO:0030199), as well as collagen-related cellular components, such as collagen-rich ECM (GO:0062023) and collagen trimers (GO:0005581), and collagen-related molecular functions (such as collagen binding (GO:0005518)). The modular heat map showed that genes encoding ECM proteins were significantly upregulated in defects treated with WPU patches. These genes included collagen types I, III, and V (COL1A1, COL3A1, and COL5A1), fibronectin 1 (FN1), fibrillins (FBN1 and FBN2), and ECM1, which are mainly involved in the formation of wound granulation tissue. After WPU patch treatment, some genes encoding key proteins of the mucosal basement membrane showed high expression levels, such as collagen IV (COL4A2), nestin (NID1), laminin (LAMA3 and LAMB1), and collagen XVII (COL17A1, a key molecule for keratinocyte adhesion). This increase in expression may indicate that the basement membrane in the WPU patch-treated defects is restored faster, which is consistent with the active basal cell proliferation results observed by immunofluorescence staining ( Fig.21 ). In addition, genes involved in cell-cell and cell-matrix interactions were upregulated in the WPU group. These genes included integrin family genes (integrin β1 (ITGB1), integrin α11 (ITGA11), and integrin αv (ITGAV)), thrombospondin 2 (TNBS2), and periostin (POSTN), which play important roles in cell adhesion, migration, and proliferation.

[0189] The epithelialization module includes various aspects of epidermal and keratin development. 51 significantly altered GO pathways were found in the WPU vs. control comparison and 38 pathways were found in the WPU vs. dECM comparison ( Figure 5aC). Many highly expressed genes in the WPU patch-treated defects are involved in cell differentiation processes, such as epithelial and keratinocyte differentiation (GO: 0030855, 0030216; KRT10, KRT14, intracellular protein (IVL), TP63, KLF4, SOX11, PITX2, WNT5A, WNT16, and NOTCH1) and epithelial and keratinocyte development (GO: 0060429, 0003334; WNT3, WNT11, WNT5A, TP63, and KDF1). During epidermal remodeling, KRT14-expressing progenitor cells are located in the basal layer, where they actively multiply, migrate upward, and differentiate into mature keratinocytes, expressing the marker proteins KRT10 and IVL after differentiation. The transcription factor TP63 encodes the tumor protein p63, which is a specific marker for epidermal and keratinocyte stem cells and is responsible for proliferation and regeneration during epithelialization. The SOX transcription factor family is essential for embryonic development. For example, SOX11 converts differentiated epidermal cells back to an embryonic-like state, which is required for the re-epithelialization process of wound healing. The upregulation of these genes suggests that WPU patch treatment may be associated with wound-induced stem cell gene activation. Genes involved in cell proliferation and migration showed higher expression levels in WPU patch-treated defects compared with other treatments (GO: 0050673, 0090132, 0043616, 0051546; WNT3A, WNT5A, epidermal growth factor receptor (EGFR), transforming growth factor alpha (TGFA), amphiregulin (AREG), epidermal regulin (EPR), SOX11, and Notch1). The Wnt signaling pathway controls a variety of epidermal stem cells in the basal layer or hair follicles, is essential for skin development and homeostasis, and regulates adult skin proliferation. EGFR activation plays a vital role in re-epithelialization by accelerating keratinocyte migration and proliferation near the wound edge, and its ligands are from the EGF family (including TGF-α, EPR and AREG), which can effectively promote wound repair. The genes in these three modules are widely upregulated during proliferation, driving a series of cellular responses, including migration, proliferation and differentiation, which promotes the formation of wound granulation and re-epithelialization in defects treated with WPU patches.

[0190] In addition, KEGG analysis of DEGs revealed that several signaling pathways closely related to defect repair were upregulated in the defects treated with WPU patches ( Figure 5bD, E), including calcium signaling pathway (Entry ID: 04020), Hippo signaling pathway (04390), and Wnt signaling pathway (04310), which are key pathways for promoting cell proliferation and resisting cell apoptosis after trauma; and PPAR signaling pathway (03320), which contributes to the differentiation of lipofibroblasts and the deposition of collagen ECM in the defect. Calcium ions are both intracellular second messengers and extracellular signaling molecules, guiding various cells such as keratinocytes and fibroblasts to participate in defect healing. Calcium pathways regulate the expression of specific keratinocyte differentiation markers, including KRT1, KRT10, and IVL, which showed high expression levels in the WPU group. In the Wnt pathway, the gene expression of upstream Wnt family members (WNT3, WNT5, WNT11, etc.), transmembrane proteins (FZD2 and FZD10), intracellular components (DVL and AXIN1), and downstream components (MYC, Jun, and FOSL1) were all upregulated with WPU patch treatment. The downstream proto-oncogene MYC is closely related to cell proliferation and stimulation of epidermal stem cell differentiation. JUN is the main component of AP-1 heterodimer, promoting the synthesis of ECM, and mainly affecting multiple fibroblast subsets responsible for wound granulation formation. In addition, the expression of several key DEGs was confirmed by RT-qPCR ( Figure 5b F). Consistent with the RNA-seq results, higher mRNA expression of WNT5A, MYC, TP63, KRT10, transcription factors (SOX11 and PITX1, both identified in oral mucosa and skin as important factors for reprogramming keratinocytes to improve wound repair), and epidermal growth factor (EGF) were found in the defects treated with WPU patches compared with the other two groups.

[0191] In summary, the WPU patch treatment activated multiple converging pro-healing signals and simultaneously modulated the immune microenvironment. This could explain why defect healing occurred primarily through granulation tissue formation and re-epithelialization. In contrast, in the other treatment groups, persistent inflammation and obstruction of regenerative signals led to defect closure primarily through contraction rather than tissue remodeling.

[0192] Corrects the contraction-dependent healing process and promotes scar-free oral mucosal remodeling

[0193] It is generally believed that early wound contraction is one of the main causes of late scar formation. The WPU patch treatment in this embodiment can effectively block the healing process that depends on contraction by promoting the rapid formation of new tissue in the proliferation phase, and the blockage of contraction is expected to induce subsequent scar-free mucosal remodeling. In addition, during this rapid new tissue formation process, the isotropic porous structure of the WPU patch in three-dimensional space can guide the collagen-rich ECM to be deposited in a "basket weaving" manner, and further avoid the formation of scar-like oriented collagen fibers. Therefore, this embodiment studies the changes in cellular and molecular events related to ECM synthesis and scar formation in the transition from the proliferation phase (4-21 days) to the remodeling phase (21 days to several months) to evaluate the effects of early anti-inflammatory and contraction blocking on late scar formation. Fibroblasts, especially myofibroblasts that express α-smooth muscle actin (α-SMA) after differentiation, are mainly responsible for synthesizing collagen-rich ECM and play a key role in repairing damaged mucosal matrix. Myofibroblasts initially appear in early granulation tissue and gradually decrease with the advancement of normal healing. Once they become overactivated, accompanied by overexpression of α-SMA, scar contracture will occur to a large extent. Immunofluorescence staining showed that in the proliferation period (14 days after wound healing), the degree of differentiation of myofibroblasts in the defects treated with WPU patch was higher than that in the other two groups ( Figure 6 A). However, after entering the tissue remodeling period (day 28), α-SMA staining in the WPU group dropped significantly to near normal levels. In contrast, in the control group and the defects treated with dECM, the number of myofibroblasts increased significantly, and contractile myofibroblasts gathered around the defect boundary and arranged parallel to the epidermal plane, forming a contractile stress field that caused the boundary to contract ( Figure 6 A). At the same time, strong staining of transforming growth factor-β (TGF-β, a growth factor that directly stimulates myofibroblast differentiation and scar hyperplasia) was also observed in both groups ( Figure 6 B). These results suggest that in WPU patch-treated defects, α-SMA expression initially increases and then decreases, thus promoting restoration of the mucosal matrix while reducing the risk of fibrosis. Figure 3 G), another notable feature of scarless wound healing is the high ratio of type III collagen to type I collagen in the regenerated matrix. Immunofluorescence analysis showed that this ratio in the WPU group was close to normal and significantly higher than that in the other two groups (compared with the control group, P = 0.0039; compared with dECM, P = 0.0198; Figure 6 C). This indicates that the newly synthesized matrix in the WPU patch-treated defect has collagen assembly structure and composition characteristics consistent with normal oral mucosa. During the proliferation phase, the GO gene module of collagen matrix deposition in the WPU group was upregulated to promote the formation of wound granulation tissue ( Figure 5aB). However, long-term activation of this module will lead to excessive deposition of ECM and fibrotic scar formation. Therefore, during the remodeling period, RNA-seq was used to continuously track the changes of all genes in this module in two comparison groups (WPU vs. control group and WPU vs. dECM). Hierarchical clustering results showed that many genes related to ECM and fibrosis were downregulated in the WPU group 28 days after surgery ( Figure 6 D), which is in stark contrast to their previous upregulation during the proliferation phase (14 days). At 12 weeks after surgery, WPU patch-treated defects showed significant changes in GO pathways belonging to the collagen matrix module compared with control defects or dECM-treated defects, with a more pronounced downregulation of the collagen matrix deposition module, including downregulation of genes encoding ECM proteins such as COL1A2, COL3A1, LAMA1, ECM1, and FN1. Real-time quantitative polymerase chain reaction (RT-qPCR) results ( Figure 6 E) confirmed the downregulation of ECM protein genes (COL1A2, ECM1, and FN1) in the WPU-treated group from proliferation (day 14) to remodeling (day 28). Among them, the upregulation of COL3A1 on day 28 may be related to the higher ratio of type III / type I collagen in this group found by immunofluorescence ( Figure 6 C). The expression trend of TGFB1 gene is consistent with the fluorescence staining results of α-SMA and TGF-β ( Figure 6 A, 6B). Despite the potential role of hypoxia-inducible factor-1 (HIF-1) in wound healing, especially angiogenesis, the sustained activation of HIF-1A exacerbates fibrotic disease. A significant downregulation of HIF-1A expression was observed in WPU patch-treated defects 28 days after surgery. In contrast, the expression of thrombospondin (THBS1), a scar ECM glycoprotein, was increased in the dECM group at day 28, which may activate TGF-β1 to mediate fibrosis. In addition, the abnormal expression of aggrecan (ACAN, a cartilage proteoglycan) in both control and dECM-treated defects may indicate the misdifferentiation of scar-associated fibroblasts.

[0194] The closure of defects requires three processes: wound contraction, scar formation and regeneration. Fibrotic scars are the product of wound contraction, which leads to irreversible tissue loss in the original anatomical site, hindering regeneration in space and time. This may eventually lead to organ dysfunction, such as limited mouth opening. The experimental results of the present invention show that the WPU patch of the present invention can accelerate the formation of new tissue by reducing inflammation and widely activating pro-healing signals. The WPU patch of the present invention can hinder the early contracture of the wound, thereby promoting a smooth transition from the proliferative phase to scarless tissue remodeling, thereby promoting defect healing and mucosal regeneration. In contrast, in the control group and the defects treated with dECM, the disorder of the healing process (including persistent inflammation and delayed regeneration signals) may induce early contraction of the wound and lead to excessive deposition of ECM during the remodeling process, ultimately forming a fibrotic scar. Through multiple experimental characterizations and verifications, the porous regenerative scaffolds prepared by the universal semi-solid freeze-casting technology applicable to a variety of biomaterials provided by the present invention are not limited by size or shape, and can be mass-produced into large-sized porous scaffolds with uniform isotropic porous structures, which is helpful for constructing structurally controllable multi-layer tissue patches and applying them to wounds of different degrees (such as preclinical studies of small to large animals, clinical applications (such as large-area burn wounds)).

[0195] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a porous scaffold, characterized in that: The method comprises: S101 dynamically freezes the precooled first mixture, wherein the dynamic freezing method includes adding liquid nitrogen to the first mixture while stirring to obtain a second mixture, wherein the second mixture is in a semi-solid ice slurry state, and the second mixture is a solid-liquid-gas three-phase mixture, wherein the volume of the liquid nitrogen is 2-3 times the volume of the first mixture, and the stirring includes a first stirring stage and a second stirring stage; in the first stirring stage, a first volume of the liquid nitrogen is added and stirred at a first stirring rate for t1 time, and in the second stirring stage, a second volume of the liquid nitrogen is added and stirred at a second stirring rate for t2 time; S102 adding the second mixture into a mold and placing the mold until the second mixture is completely solidified to obtain a third mixture; S103 freeze-drying the third mixture to obtain the porous scaffold; Wherein, the first mixture includes an aqueous solution, emulsion or suspension of a bioactive material, the bioactive material includes polyurethane, the addition rate of the liquid nitrogen includes 0.5-10 mL / min, the first stirring rate includes 200-300 rpm, the t1 time includes 2-5 min, and the first volume includes 30%-45% of the volume of the liquid nitrogen; the second stirring rate includes 400-600 rpm, the t2 time includes 5-8 min, and the second volume includes 55%-70% of the volume of the liquid nitrogen.

2. The method according to claim 1, characterized in that The pre-cooling temperature includes 2 - 4°C.

3. The method according to claim 1, characterized in that The second mixture was placed at -30°C – -10°C.

4. The method according to claim 1, wherein: The stirring also includes a third stirring stage, which includes adding an additional third volume of the liquid nitrogen to the first mixture and stirring at a third stirring rate for a time t3, wherein the third stirring rate includes 900-1200 rpm, the t3 time includes 5-8 min, and the third volume includes 45%-55% of the total volume of the liquid nitrogen added in the first stirring stage and the second stirring stage.

5. The method according to claim 1, wherein The bioactive material is a polyethylene glycol-based waterborne polyurethane, wherein the percentage of polyethylene glycol in the polyethylene glycol-based waterborne polyurethane soft segment is 15-30 mol%.

6. The method according to claim 5, characterized in that The solid content of the polyethylene glycol-based waterborne polyurethane comprises 10-40 wt%.

7. A porous patch for tissue regeneration, characterized in that: The patch comprises: A bottom support layer, the bottom support layer comprising the porous support prepared by the method according to any one of claims 1 to 6; a top barrier layer, the top barrier layer being used to protect the bottom support layer and / or provide mechanical support for the bottom support layer; The thickness of the bottom support layer is 2-10 mm, and the thickness of the top barrier layer is 0.2-0.8 mm.

8. The patch according to claim 7, characterized in that The top barrier layer is prepared by coating a polymer emulsion onto the porous support layer and then drying the emulsion. The solid content of the polymer emulsion is 50-70 wt %, and the polymer includes one or more of polycaprolactone-based waterborne polyurethane, polycaprolactone and lactide-co-glycolide copolymer.

Citation Information

Patent Citations

  • Bioabsorbable dermal regeneration matrix and methods of making and using same

    US20190160198A1

  • Method for preparing a porous polymer scaffold using dry ice

    WO2008130068A1